Polyphenylene ether, polyphenylene ether solution, resin film, prepreg, and metal-clad laminate

By combining polyphenylene ether A derived from specific phenol with ingredients such as triallyl isocyanurate and organic peroxide, an optimized resin composition is formed, and the problems of insufficient solubility of polyphenylene ether at room temperature and insufficient performance of the resin composition are solved, and efficient dissolution and excellent performance are achieved.

CN119875110AActive Publication Date: 2025-04-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510074582.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-20
Filing Date
2024-10-21
Publication Date
2025-04-25
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The prior art is difficult to dissolve polyphenylene ether at high concentration at room temperature, and the copper foil peel strength and toluene resistance of the cured resin composition are insufficient.

Method used

Polyphenylene ether A containing derived from specific phenol repeat units and combined with ingredients such as triallyl isocyanurate and organic peroxide to form an optimized resin composition.

Benefits of technology

The high solubility of polyphenylene ether in toluene is achieved, and the copper foil peel strength, toluene resistance, dielectric properties and heat resistance of the cured resin composition are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875110A_ABST
    Figure CN119875110A_ABST
Patent Text Reader

Abstract

The invention relates to polyphenyl ether, a polyphenyl ether solution, a resin film, a prepreg and a metal-clad laminated board. A polyphenylene ether which contains a prescribed amount of repeating units derived from a phenol represented by formula (1) and a prescribed amount of repeating units derived from a phenol represented by formula (2), and which has a molecular weight distribution (Mw / Mn) of 2.0-6.0 and a number of OH groups per molecule of 0.8-2.5 per molecule. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the original application is 202411465436.8, the application date is October 21, 2024, and the name of the invention is "Resin composition, resin film, prepreg and metal-clad laminate". Technical Field

[0002] The present invention relates to a resin composition, a resin film, a prepreg and a metal-clad laminate. Background Art

[0003] Polyphenylene ether (hereinafter also referred to as "PPE") has excellent high-frequency characteristics, flame retardancy, and heat resistance, and is therefore widely used as a material for products / parts in the electrical-electronic field, the automotive field, the food-packaging field, and various other industrial materials. In recent years, in particular, its low dielectric properties and heat resistance have been used to promote its use as a modifier in various applications including electrical and electronic applications such as substrate materials.

[0004] However, high molecular weight polyphenylene ethers generally having repeating units derived from monovalent phenols represented by 2,6-dimethylphenol are soluble in highly toxic solvents such as chloroform, but have the following problems: they are difficult to dissolve at high concentrations at room temperature even in aromatic solvents such as toluene, which are known as good solvents, and are insoluble in ketone solvents such as methyl ethyl ketone. Therefore, when used as wiring board materials, for example, it is difficult to handle in resin varnish solutions such as toluene and methyl ethyl ketone.

[0005] Patent Document 1 discloses a resin composition in which a varnish is prepared by heating and melting polyphenylene ether in an aromatic solvent in order to improve the solubility and dispersibility of polyphenylene ether.

[0006] Patent Document 2 discloses a polyphenylene ether having excellent solubility in a general-purpose ketone solvent and a thermosetting composition using the polyphenylene ether.

[0007] Furthermore, Patent Document 3 discloses a resin composition containing a low molecular weight polyphenylene ether component obtained by redistribution reaction of a high molecular weight polyphenylene ether and a monofunctional or polyfunctional phenol, a crosslinking agent, and an organic peroxide.

[0008] Patent Document 4 discloses a thermosetting composition containing a polyphenylene ether having a specific molecular weight and having an ethylidene benzyl group at a terminal, a polyphenylene ether having a specific molecular weight, and a trialenyl isocyanurate.

[0009] Patent Document 5 discloses a resin composition containing a polymer polyphenylene ether, a crosslinking agent, and an organic peroxide, wherein a low molecular weight polyphenylene ether component obtained by redistribution reaction between a polymer polyphenylene ether and a monofunctional or polyfunctional phenol is terminally modified.

[0010] Patent Document 6 discloses a resin composition comprising two terminally modified low-molecular polyphenylene ethers having different skeletons and a cross-linking curing agent.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent No. 3151397

[0014] Patent Document 2: International Publication No. 2022 / 158180

[0015] Patent Document 3: Japanese Patent No. 7202920

[0016] Patent Document 4: Japanese Patent No. 4900315

[0017] Patent Document 5: Japanese Patent No. 4211784

[0018] Patent Document 6: Japanese Patent No. 7203386 Summary of the invention

[0019] Problems to be solved by the invention

[0020] However, even when the resin composition described in Patent Document 1 is used, a resin composition containing polyphenylene ether soluble in toluene at room temperature (having solvent solubility) cannot be obtained, and the copper foil peel strength and toluene resistance of the cured resin composition also have further problems to be solved.

[0021] When the resin composition described in Patent Document 2 is used, a polyphenylene ether having excellent solubility in organic solvents such as toluene and methyl ethyl ketone can be obtained, but there is no disclosure on the copper foil peel strength and toluene resistance of the cured resin composition.

[0022] Furthermore, the polyphenylene ether obtained by the redistribution reaction disclosed in Patent Document 3 generally contains an organic peroxide used for the redistribution reaction, and the organic peroxide remaining in the product may adversely affect the dielectric properties of the substrate.

[0023] Furthermore, in the composition disclosed in Patent Document 4, the solubility when made into a varnish has a further problem to be solved.

[0024] Furthermore, the polyphenylene ether obtained by the redistribution reaction disclosed in Patent Document 5 generally contains an organic peroxide used for the redistribution reaction, and the organic peroxide remaining in the product may adversely affect the dielectric properties of the substrate.

[0025] In the resin composition disclosed in Patent Document 6, compared with the resin composition using each terminal-modified low-molecular-weight polyphenylene ether alone, there is a simple trade-off relationship, and no improvement in dielectric properties, copper foil peel strength, etc. is observed by using two terminal-modified low-molecular-weight polyphenylene ethers together.

[0026] The present invention has been made in view of the above problems, and an object of the present invention is to provide a resin composition containing polyphenylene ether having excellent solvent solubility and having excellent copper foil peel strength, toluene resistance, dielectric properties, and heat resistance.

[0027] Another object of the present invention is to provide a resin film, a prepreg, and a metal-clad laminate formed using the resin composition.

[0028] Means for solving problems

[0029] That is, the present invention is as follows.

[0030] (1) A resin composition comprising:

[0031] (A) polyphenylene ether A;

[0032] (B) triallyl isocyanurate and / or triallyl cyanurate;

[0033] (B') as an optional component a crosslinking agent other than triallyl isocyanurate and triallyl cyanurate; and

[0034] (C) organic peroxides,

[0035] The resin composition is characterized in that

[0036] The polyphenylene ether (A) A comprises repeating units derived from phenol of the following formula (1) and repeating units derived from phenol of the following formula (2).

[0037] With respect to 100 mol % of the total of the repeating units of the following formula (1) and the following formula (2), the content of the repeating units derived from the phenol of the following formula (1) is 55 mol % or more and less than 90 mol %, and the content of the repeating units derived from the phenol of the following formula (2) is greater than 10 mol % and less than 45 mol %,

[0038] The molecular weight distribution (Mw / Mn) determined by gel permeation chromatography (GPC) is 2.0 to 6.0 or less,

[0039] The number of OH groups per molecule is 0.8 to 2.5.

[0040] [Chemistry 1]

[0041]

[0042] (In formula (1), R 11 are each independently a saturated hydrocarbon group having 1 to 6 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom, and R 12 Each is independently a hydrogen atom, a hydrocarbon group having 1 to 6 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom.

[0043] [Chemistry 2]

[0044]

[0045] (In formula (2), R 22 are each independently a hydrogen atom, a saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom, and the two R 22 If they are not hydrogen atoms, R 21 It is a partial structure represented by the following formula (3).

[0046] [Chemistry 3]

[0047]

[0048] (In formula (3), R 31 Each independently represents a linear alkyl group having 1 to 8 carbon atoms which may be substituted, or two R 31 A cyclic alkyl structure having 1 to 8 carbon atoms, R 32 are each independently an alkylene group having 1 to 8 carbon atoms which may have a substituent, b is each independently 0 or 1, R 33 is a hydrogen atom, an alkyl group having 1 to 8 carbon atoms which may have a substituent, or a phenyl group which may have a substituent.

[0049] (2) A resin composition as described in (1), characterized in that, in the above-mentioned (A) polyphenylene ether A, the content of repeating units derived from phenol of the following formula (1) is 70 mol% or more and less than 85 mol% relative to 100 mol% of the total of repeating units of the following formula (1) and the following formula (2), and the content of repeating units derived from phenol of the following formula (2) is greater than 15 mol% and less than 30 mol%.

[0050] (3) The resin composition according to (1) or (2), wherein the partial structure represented by the formula (3) is a tert-butyl group.

[0051] (4) The resin composition according to any one of (1) to (3), wherein the polyphenylene ether (A) has a reduced viscosity (ηsp / c) of 0.13 to 0.30 dL / g as measured in a 0.5 g / dL chloroform solution at 30°C.

[0052] (5) The resin composition according to any one of (1) to (4), wherein the number of OH groups per 1 g of the polyphenylene ether (A) is 100 to 450 μmol / g.

[0053] (6) The resin composition according to any one of (1) to (4), wherein the number of OH groups per 1 g of the polyphenylene ether (A) is 100 to 300 μmol / g.

[0054] (7) The resin composition according to any one of (1) to (6), wherein the mass ratio (A:B) of the polyphenylene ether (A) to the triallyl isocyanurate and / or triallyl cyanurate (B) is 50:50 to 80:20.

[0055] (8) The resin composition as described in any one of (1) to (7), characterized in that it contains 0.05 mass parts or more and 10 mass parts or less of the organic peroxide (C) relative to 100 mass parts of the total of the (A) polyphenylene ether A, the (B) triallyl isocyanurate and / or triallyl cyanurate, and the (B') cross-linking agent other than triallyl isocyanurate and triallyl cyanurate.

[0056] (9) The resin composition according to any one of (1) to (7), characterized in that it contains 1.0 part by mass or more and 5.0 parts by mass or less of the organic peroxide (C) relative to 100 parts by mass of the total of the (A) polyphenylene ether A, the (B) triallyl isocyanurate and / or triallyl cyanurate, and the (B′) cross-linking agent other than triallyl isocyanurate and triallyl cyanurate.

[0057] (10) The resin composition according to any one of (1) to (9), characterized in that it contains 0.1 parts by mass or more and 50 parts by mass or less of the organic peroxide (C) relative to 100 parts by mass of the total of the (B) triallyl isocyanurate and / or triallyl cyanurate and (B') a cross-linking agent other than triallyl isocyanurate and triallyl cyanurate.

[0058] (11) The resin composition according to any one of (1) to (10), wherein the one-minute half-life temperature of the organic peroxide (C) is 155°C to 195°C.

[0059] (12) The resin composition according to any one of (1) to (11), further comprising (D) a polyfunctional methacrylic compound.

[0060] (13) A resin composition as described in (12), characterized in that the content of the above-mentioned (A) polyphenylene ether A is not less than 40 mass % and not more than 80 mass % relative to 100 mass parts of the total amount of the above-mentioned (A) polyphenylene ether A, the above-mentioned (B) triallyl isocyanurate and / or triallyl cyanurate and the above-mentioned (D) polyfunctional methacrylic compound.

[0061] (14) A resin composition as described in (12) or (13), characterized in that the content of the above-mentioned (D) multifunctional methacrylic compound is not less than 20 mass % and not more than 80 mass % relative to 100 mass parts of the total amount of the above-mentioned (B) triallyl isocyanurate and / or triallyl cyanurate and the above-mentioned (D) multifunctional methacrylic compound.

[0062] (15) A resin composition as described in any one of (1) to (14), characterized in that it further comprises (E) a polyphenylene ether B, which comprises repeating units derived from the phenol of the above formula (1) and has at least one partial structure selected from the group consisting of the following formulas (4), (5), (6) and (7) in its molecular skeleton (but excluding a structure equivalent to the above polyphenylene ether A).

[0063] [Chemistry 4]

[0064]

[0065] [Chemistry 5]

[0066]

[0067] [Chemistry 6]

[0068]

[0069] (In formula (6), R 6 It is a hydrogen atom or a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms. The saturated or unsaturated hydrocarbon group may have a substituent as long as the number of carbon atoms is 1 to 10.

[0070] [Chemistry 7]

[0071]

[0072] (In formula (7), R 7 is a saturated or unsaturated divalent hydrocarbon group having 1 to 10 carbon atoms. The saturated or unsaturated divalent hydrocarbon group may have a substituent as long as the number of carbon atoms is 1 to 10.8 It is a hydrogen atom or a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms. The saturated or unsaturated hydrocarbon group may have a substituent as long as the number of carbon atoms is 1 to 10.

[0073] (16) The resin composition according to (15), wherein the polyphenylene ether (E) B further comprises a structural unit derived from phenol represented by the following formula (8).

[0074] [Chemistry 8]

[0075]

[0076] (In formula (8), X is an arbitrary a-valent linking group, a is an integer from 2 to 6, and R 9 is any one of a linear alkyl group having 1 to 8 carbon atoms and the partial structure represented by the above formula (3), wherein the carbon atom of the benzene ring to which -O- is bonded is at position 1, and the R 9 It is bonded to at least one carbon atom at the 2-position or the 6-position, and k is an integer of 1 to 4 for each independently.

[0077] R in the above formula (8) 9 The partial structure represented by the above formula (3) and R in the above formula (2) 21 The partial structures represented by the above formula (3) may be the same or different.

[0078] (17) The resin composition according to (15) or (16), wherein the polyphenylene ether (E) B further comprises a repeating unit derived from phenol of the formula (2).

[0079] (18) The resin composition according to any one of (15) to (17), wherein the mass ratio (A:E) of the polyphenylene ether (A) to the polyphenylene ether (E) B is 80:20 to 20:80.

[0080] (19) A resin film comprising the resin composition according to any one of (1) to (18).

[0081] (20) A prepreg characterized by being a composite of a substrate and the resin composition according to any one of (1) to (18).

[0082] (21) The prepreg according to (20), wherein the substrate is glass cloth.

[0083] (22) A metal-clad laminate, characterized in that it is a laminate of a cured product of the resin film described in (19) and a metal foil.

[0084] (23) A metal-clad laminate, characterized in that it is a laminate of a cured product of the prepreg according to (20) or (21) and a metal foil.

[0085] Effects of the Invention

[0086] According to the present invention, a polyphenylene ether resin composition having excellent copper foil peel strength, toluene resistance, dielectric properties, and heat resistance can be provided.

[0087] Furthermore, according to the present invention, there can be provided an electronic circuit board material, a resin film, a prepreg, and a metal-clad laminate formed using the polyphenylene ether resin composition. DETAILED DESCRIPTION

[0088] The specific implementation mode of the present invention (hereinafter referred to as "this implementation mode") is described in detail below. The following implementation mode is an example for explaining the present invention, and the present invention is not limited to this implementation mode, and the present invention can be implemented by appropriately deforming within the scope of the gist thereof.

[0089] In the present embodiment, polyphenylene ether in which part or all of the hydroxyl groups contained in the polyphenylene ether are modified may be simply expressed as “polyphenylene ether.” Therefore, when expressed as “polyphenylene ether,” both unmodified polyphenylene ether and modified polyphenylene ether are included unless there is any particular contradiction.

[0090] In the present specification, A (numerical value) to B (numerical value) refer to A or more and B or less. In the present specification, a substituent refers to, for example, a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen atom, and the like.

[0091] <Resin composition>

[0092] The resin composition of the present embodiment is a resin composition comprising (A) polyphenylene ether A, (B) triallyl isocyanurate and / or triallyl cyanurate, (B′) a crosslinking agent other than triallyl isocyanurate and triallyl cyanurate as an optional component, and (C) an organic peroxide.

[0093] (Polyphenylene ether A)

[0094] The polyphenylene ether A contains at least repeating units derived from phenol of the following formula (1) and repeating units derived from phenol of the following formula (2), and may be composed only of repeating units derived from phenol of the following formula (1) and repeating units derived from phenol of the following formula (2).

[0095] [Chemistry 9]

[0096]

[0097] (In formula (1), R11 are each independently a saturated hydrocarbon group having 1 to 6 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom, and R 12 Each is independently a hydrogen atom, a hydrocarbon group having 1 to 6 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom.

[0098] [Chemistry 10]

[0099]

[0100] (In formula (2), R 22 are each independently a hydrogen atom, a saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom, and the two R 22 If they are not hydrogen atoms, R 21 It is a partial structure represented by the following formula (3).

[0101] [Chemistry 11]

[0102]

[0103] (In formula (3), R 31 Each independently represents a linear alkyl group having 1 to 8 carbon atoms which may be substituted, or two R 31 A cyclic alkyl structure having 1 to 8 carbon atoms, R 32 are each independently an alkylene group having 1 to 8 carbon atoms which may have a substituent, b is each independently 0 or 1, R 33 is a hydrogen atom, an alkyl group having 1 to 8 carbon atoms which may have a substituent, or a phenyl group which may have a substituent.

[0104] In the above formula (1), R 11 Each of the two R groups independently is preferably a saturated hydrocarbon group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms, more preferably a methyl group or a phenyl group, and still more preferably a methyl group. 11 Preferably, they are of the same structure.

[0105] In the above formula (1), R 12 Each of the two R is independently preferably a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms, and more preferably a hydrogen atom or a methyl group. 12 Preferably, they are different, and more preferably, one is a hydrogen atom and the other is a hydrocarbon group having 1 to 6 carbon atoms (preferably a methyl group).

[0106] In the above formula (2), R 22Each independently is preferably a hydrogen atom, a saturated or unsaturated hydrocarbon group having 1 to 15 carbon atoms, or an aryl group having 6 to 12 carbon atoms which may be substituted with an alkyl group having 1 to 6 carbon atoms, more preferably a hydrogen atom, a hydrocarbon group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms which may be substituted with an alkyl group having 1 to 6 carbon atoms, and still more preferably a hydrogen atom or a methyl group. 22 Preferably, they are different, and more preferably, one is a hydrogen atom and the other is a hydrocarbon group having 1 to 6 carbon atoms (preferably a methyl group).

[0107] The partial structure represented by the above formula (3) is preferably a group containing secondary carbon and / or tertiary carbon, for example, isopropyl, isobutyl, sec-butyl, tert-butyl, tert-amyl, 2,2-dimethylpropyl, cyclohexyl, and structures having phenyl groups at their terminals, more preferably tert-butyl and cyclohexyl, and still more preferably tert-butyl.

[0108] In this embodiment, the structure of the polyphenylene ether A can be identified by analyzing by methods such as NMR and mass analysis. As a specific method for identifying the structure of the polyphenylene ether A, field desorption mass spectrometry (FD-MS), which is known to be less likely to generate fragments, can be implemented to estimate the repeating unit by the interval between the detected ions. Further, a method for estimating the structure of the polyphenylene ether A by combining peak analysis of fragment ions using electron ionization (EI) and structural analysis based on NMR can be cited.

[0109] Furthermore, in the present embodiment, the polyphenylene ether A comprises repeating units derived from phenol of the above formula (1) and repeating units derived from phenol of the above formula (2), and the content of the repeating units derived from phenol of the above formula (1) is 55 mol% or more and less than 90 mol% relative to 100 mol% of the total of the repeating units of the above formula (1) and the above formula (2), and the content of the repeating units derived from phenol of the above formula (2) is greater than 10 mol% and less than 45 mol%.

[0110] The polyphenylene ether A contains repeating units derived from phenol of the formula (1) and repeating units derived from phenol of the formula (2) in the above ratio, so that the polyphenylene ether A has excellent solvent solubility and improves the copper foil peel strength and toluene resistance of the substrate.

[0111] From the same perspective, in the polyphenylene ether A, with respect to 100 mol% of the total of the repeating units of the formula (1) and the formula (2), preferably, the content of the repeating units derived from the phenol of the formula (1) is 60 mol% or more and less than 85 mol%, and the content of the repeating units derived from the phenol of the formula (2) is greater than 15 mol% and less than 40 mol%; more preferably, the content of the repeating units derived from the phenol of the formula (1) is 70 mol% or more and less than 85 mol%, and the content of the repeating units derived from the phenol of the formula (2) is greater than 15 mol% and less than 30 mol%; further preferably, the content of the repeating units derived from the phenol of the formula (1) is 100 mol% or more and less than 85 mol%, and the content of the repeating units derived from the phenol of the formula (2) is greater than 15 mol% and less than 30 mol%; The content of repeating units is 72 mol% to 84 mol%, and the content of repeating units derived from phenol of the above formula (2) is 16 mol% to 28 mol%; more preferably, the content of repeating units derived from phenol of the above formula (1) is 74 mol% to 83.5 mol%, and the content of repeating units derived from phenol of the above formula (2) is 16.5 mol% to 26 mol%; particularly preferably, the content of repeating units derived from phenol of the above formula (1) is 75 mol% to 83 mol%, and the content of repeating units derived from phenol of the above formula (2) is 17 mol% to 25 mol%.

[0112] Since the phenol of the above formula (1) has no unsubstituted ortho positions (i.e., since no hydrogen atoms are bonded to the two ortho carbon atoms of the carbon atom to which the hydroxyl group is bonded), it can react with other phenolic monomers only at the carbon atom para to the phenolic hydroxyl group. Therefore, the repeating unit derived from the above formula (1) includes a repeating unit having a structure of the following formula (9).

[0113] [Chemistry 12]

[0114]

[0115] (In formula (9), R 11 and R 12 Same as in formula (1).

[0116] In the phenol of the above formula (2), in addition to the phenolic hydroxyl group, any position of the ortho or para position of the phenol can react with other phenolic monomers. Therefore, the repeating unit derived from the phenol of the formula (2) has the structure of the following formula (10), the following formula (11), or a combination thereof.

[0117] [Chemistry 13]

[0118]

[0119] [Chemistry 14]

[0120]

[0121] (R in formula (10) and formula (11) 21 , R 22 Same as in formula (2).

[0122] Furthermore, the polyphenylene ether A may include a structural unit derived from phenol represented by the following formula (8).

[0123] [Chemistry 15]

[0124]

[0125] (In formula (8), X is an arbitrary linking group with a valence of a, a is an integer of 2 to 6, and R 9 is any one of a linear alkyl group having 1 to 8 carbon atoms and the partial structure represented by the above formula (3), wherein the carbon atom of the benzene ring to which -O- is bonded is at position 1, and the R 9 Bonded to at least one carbon atom at the 2-position or 6-position, and k is each independently an integer of 1 to 4.

[0126] In the above formula (8), R 9 Each is independently a linear alkyl group having 1 to 8 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, and any one of the partial structures represented by the above formula (3), preferably a methyl group or the structure of the above formula (3). The a individual partial structures may be the same structure or different. Among them, from the perspective of obtaining a polyphenylene ether A having better solubility in a solvent and a higher glass transition temperature after curing, it is preferred that the a individual partial structures are the same structure.

[0127] In the above formula (8), k is an integer of 1-4, preferably an integer of 2-4.

[0128] In the above formula (8), the carbon atom of the benzene ring to which -O- is bonded is at position 1, and R 9 Bonded to at least one carbon atom at the 2-position and the 6-position, bonded to R at the 2-position and / or the 6-position 9 In the case of a linear alkyl group having 1 to 8 carbon atoms, it is preferably bonded to both the 2-position and the 6-position, and R bonded to the 2-position and / or the 6-position 9 In the case of the partial structure represented by formula (3), it is preferably bonded only to the 2-position or the 6-position.

[0129] The polyphenylene ether A may include a repeating unit derived from the formula (8), a repeating unit derived from the phenol of the formula (1), and / or a repeating unit derived from the phenol of the formula (2).

[0130] At this time, R in the above formula (2) 21 R 9In the case where both are partial structures (functional groups) represented by formula (3) (when both the phenol compound represented by the above formula (2) and the phenol compound represented by the above formula (8) are substituted by the partial structures (functional groups) represented by the above formula (3)), the structures of the partial structures (functional groups) represented by the respective formulas (3) may be the same or different.

[0131] In the above formula (8), X is an arbitrary a-valent linking group, which is not particularly limited, but includes, for example: a hydrocarbon group such as a chain hydrocarbon or a cyclic hydrocarbon; a hydrocarbon group containing one or more atoms selected from nitrogen, phosphorus, silicon and oxygen; an atom such as nitrogen, phosphorus, silicon; or a group composed of these. X may be a linking group other than a single bond. X may be a linking group that connects a partial structures to each other.

[0132] Examples of X include: 9 The a-valent alkyl skeleton on the benzene ring to which it is bonded; bonded to R by a single bond or ester bond 9 The a-valent aromatic skeleton on the benzene ring to which it is bonded; bonded to R by a single bond or ester bond 9 An a-valent heterocyclic skeleton on the bonded benzene ring; and so on.

[0133] Here, the alkyl skeleton is not particularly limited, and examples thereof include a skeleton in which the branch end of a chain hydrocarbon (e.g., a chain saturated hydrocarbon) having 2 to 6 carbon atoms and at least a branches is directly bonded to a benzene ring of a partial structure (a branch end may be bonded to a benzene ring, or a branch end not bonded to a benzene ring may be present). In addition, the aryl skeleton is not particularly limited, and examples thereof include a benzene ring, mesityl, or 2-hydroxy-5-methyl-1,3-phenylene bonded to R by a single bond or an alkyl chain. 9 In addition, there is no particular limitation on the heterocyclic skeleton, and examples thereof include a triazine ring bonded to R via a single bond or an alkyl chain. 9 The skeleton on the bonded benzene ring, etc.

[0134] In the above formula (8), a is an integer of 2-6, preferably an integer of 2-4.

[0135] When the phenol of formula (8) does not have an unsubstituted ortho position, the structural unit derived from the phenol of formula (8) has a structure of the following formula (12); when the phenol of formula (8) has an unsubstituted ortho position, the structural unit derived from the phenol of formula (8) has a structure of the following formula (12), a structure of the following formula (13), or a combination thereof.

[0136] [Chemistry 16]

[0137]

[0138] [Chemistry 17]

[0139]

[0140] (R in formula (12) and formula (13) 9 Same as in formula (8).

[0141] The reduced viscosity (ηsp / c) of the polyphenylene ether A measured in a 0.5 g / dL chloroform solution at 30°C is 0.13 to 0.30 dL / g, preferably 0.15 to 0.28 dL / g, and more preferably 0.17 to 0.25 dL / g.

[0142] By making the reduced viscosity (ηsp / c) measured in a 0.5 g / dL concentration chloroform solution at 30°C to be 0.13 dL / g or more, high heat resistance and excellent dielectric properties derived from the polyphenylene ether A structure can be obtained. By making the reduced viscosity (ηsp / c) to be 0.30 dL / g or less, solubility in solvents such as toluene and methyl ethyl ketone can be ensured.

[0143] The reduced viscosity can be measured by the method described in the examples below.

[0144] In the polyphenylene ether A, the molecular weight distribution (Mw / Mn) determined by gel permeation chromatography (GPC) is 2.0 to 6.0, preferably 2.5 to 5.5 or less, and more preferably 3.0 to 5.0.

[0145] By making the molecular weight distribution (Mw / Mn) determined by gel permeation chromatography (GPC) to be 2.0 or more, the fluidity of the polyphenylene ether A can be improved and the reactivity during thermal curing can be increased. By making the molecular weight distribution (Mw / Mn) to be 6.0 or less, the toughness of the polyphenylene ether A can be improved, and excellent copper foil peel strength and solvent resistance of the cured product can be obtained.

[0146] As a means to make the molecular weight distribution of the above-mentioned polyphenylene ether A become the above-mentioned range, from the aspect of controlling the polymerization reactivity, the adjustment of the polymerization temperature, the adjustment of the catalyst equivalent, the adjustment of the monomer concentration in the reaction system, etc. can be cited. Among them, as a method for adjusting the monomer concentration in the reaction system, it is preferred to slowly add monomers to the reaction system. When the monomer concentration in the reaction system is high from the initial stage, it is difficult to control the molecular weight of the generated polymer due to the fast reaction rate between the monomers. On the other hand, the method of adding monomers to the reaction system by utilizing an appropriate flow rate can control the monomer concentration in the reaction system, and the reaction rate can be easily controlled. As a result, a polymer with a molecular weight distribution in a preferred range can be obtained.

[0147] Furthermore, in the present embodiment, the number of OH groups in the polyphenylene ether A is 100 to 330 μmol / g, preferably 100 to 310 μmol / g, and more preferably 100 to 300 μmol / g.

[0148] By setting the OH group number to 100 μm ol / g or more, the adhesion to the copper foil can be improved, and by setting the OH group number to 330 μm ol / g or less, the heat resistance and dielectric properties of the substrate can be improved.

[0149] It should be noted that the number of OH groups in the polyphenylene ether A can be measured by the method described in the examples described later.

[0150] In the polyphenylene ether A, the number of OH groups per molecule is 0.3 to 3.0 / molecule, preferably 0.8 to 3.0 / molecule, more preferably 0.8 to 2.8 / molecule, and even more preferably 1.0 to 2.5 / molecule.

[0151] When the number of OH groups per molecule is 0.3 or more, the adhesion to copper foil can be improved, and when the number of OH groups per molecule is 3.0 or less, the heat resistance and dielectric properties of the substrate can be improved, and the production stability of the polyphenylene ether A can be ensured.

[0152] (Polyphenylene ether B)

[0153] Furthermore, the resin composition of the present embodiment preferably further comprises (E) polyphenylene ether B, which comprises repeating units derived from phenol of the above-mentioned formula (1) and has at least one partial structure selected from the group consisting of the following formulas (4), (5), (6) and (7) in its molecular skeleton (excluding the structure corresponding to the above-mentioned polyphenylene ether A).

[0154] [Chemistry 18]

[0155]

[0156] (In the above formula (6), R 6 It is a hydrogen atom or a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms. The saturated or unsaturated hydrocarbon group may have a substituent as long as the number of carbon atoms is 1 to 10.

[0157] In the above formula (7), R 7 is a saturated or unsaturated divalent hydrocarbon group having 1 to 10 carbon atoms. The saturated or unsaturated divalent hydrocarbon group may have a substituent as long as the number of carbon atoms is 1 to 10. 8 It is a hydrogen atom or a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms. The saturated or unsaturated hydrocarbon group may have a substituent as long as the number of carbon atoms is 1 to 10.

[0158] It should be noted that the partial structure represented by at least one selected from the group consisting of the above formula (4), formula (5), formula (6), and formula (7) may be directly bonded to the oxygen of the hydroxyl group contained in the polyphenylene ether B.

[0159] The polyphenylene ether B may further include a structural unit derived from phenol represented by the following formula (8).

[0160] [Chemistry 19]

[0161]

[0162] (In the above formula (8), X is an arbitrary linking group having a valence of a, a is an integer of 2 to 6, and R 9 is any one of a linear alkyl group having 1 to 8 carbon atoms and the partial structure represented by the above formula (3), wherein the carbon atom of the benzene ring to which -O- is bonded is at position 1, and the R 9 Bonded to at least one carbon atom at the 2-position or 6-position, and k is each independently an integer of 1 to 4.

[0163] In the above formula (8), R 9 Each is independently a linear alkyl group having 1 to 8 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, and any one of the partial structures represented by the above formula (3), preferably a methyl group or the structure of the above formula (3). The a partial structures may be the same structure or different. Among them, from the perspective of obtaining a polyphenylene ether having better solubility in a solvent and a higher glass transition temperature after curing, it is preferred that the a partial structures are the same structure.

[0164] In the above formula (8), k is an integer of 1-4, preferably an integer of 2-4.

[0165] In the above formula (8), the carbon atom of the benzene ring to which -O- is bonded is at position 1, and R 9 Bonded to at least one carbon atom at the 2-position and the 6-position, and bonded to R at the 2-position and / or the 6-position 9 In the case of a linear alkyl group having 1 to 8 carbon atoms, it is preferred that the bond is at both the 2nd and 6th positions, and R 9 In the case of the partial structure represented by formula (3), it is preferably bonded only to the 2-position or the 6-position.

[0166] It should be noted that R in the above formula (2) 21 R 9In the case where both are partial structures (functional groups) represented by formula (3) (when both the phenol compound represented by the above formula (2) and the phenol compound represented by the above formula (8) are substituted by the partial structures (functional groups) represented by the above formula (3)), the structures of the partial structures (functional groups) represented by the respective formulas (3) may be the same or different.

[0167] In the above formula (8), X is an arbitrary a-valent linking group, which is not particularly limited, but for example, a hydrocarbon group such as a chain hydrocarbon or a cyclic hydrocarbon; a hydrocarbon group containing one or more atoms selected from nitrogen, phosphorus, silicon and oxygen; an atom such as nitrogen, phosphorus, silicon; or a group composed of these. X may be a linking group other than a single bond. X may be a linking group that connects a partial structures to each other.

[0168] It should be noted that the above X includes: 9 The a-valent alkyl skeleton on the benzene ring to which it is bonded; bonded to R by a single bond or ester bond 9 The a-valent aromatic skeleton on the benzene ring to which it is bonded; bonded to R by a single bond or ester bond 9 An a-valent heterocyclic skeleton on the bonded benzene ring; and so on.

[0169] Here, the alkyl skeleton is not particularly limited, and examples thereof include a skeleton in which the branch end of a chain hydrocarbon (e.g., a chain saturated hydrocarbon) having 2 to 6 carbon atoms and at least a branches is directly bonded to a benzene ring of a partial structure (a branch end may be bonded to a benzene ring, or a branch end not bonded to a benzene ring may be present). In addition, the aryl skeleton is not particularly limited, and examples thereof include a benzene ring, mesityl, or 2-hydroxy-5-methyl-1,3-phenylene bonded to R by a single bond or an alkyl chain. 9 In addition, there is no particular limitation on the heterocyclic skeleton, and examples thereof include a triazine ring bonded to R via a single bond or an alkyl chain. 9 The skeleton on the bonded benzene ring, etc.

[0170] In the above formula (8), a is an integer of 2-6, preferably an integer of 2-4.

[0171] In addition, when the phenol of the above formula (8) does not have an unsubstituted ortho position, the structural unit derived from the phenol of formula (8) has a structure of the following formula (12); when the phenol of formula (8) has an unsubstituted ortho position, the structural unit derived from the phenol of formula (8) has a structure of the following formula (12), a structure of the following formula (13), or a combination thereof.

[0172] [Chemistry 20]

[0173]

[0174] [Chemistry 21]

[0175]

[0176] (R in formula (12) and formula (13) 9 Same as in formula (8).

[0177] In addition, the polyphenylene ether B may further include a repeating unit derived from phenol of the formula (2). However, the polyphenylene ether B does not include a substance corresponding to the polyphenylene ether A (A) described above.

[0178] The number average molecular weight of the polyphenylene ether B is preferably 1,000 to 30,000, more preferably 1,500 to 25,000, and even more preferably 1,500 to 20,000.

[0179] By making the number average molecular weight of the polyphenylene ether B above 1000, toughness can be imparted to the resin composition and its cured product, and the copper foil peel strength can be improved. In addition, by making the number average molecular weight of the polyphenylene ether B below 30000, the viscosity of the varnish can be reduced and the handling property can be improved by utilizing the process of mixing the resin composition with the solvent, and the melt viscosity of the resin composition in the thermal curing process can be reduced and the crosslinking reaction speed can be increased.

[0180] The number average molecular weight of the polyphenylene ether B may be a value measured by a common molecular weight measurement method, and specifically, a value measured by GPC may be mentioned.

[0181] In this embodiment, the structure of the polyphenylene ether B can also be identified by analyzing it using NMR, mass spectrometry, etc. The specific method for identifying the structure of the polyphenylene ether is the same as that of the polyphenylene ether A.

[0182] (Method for producing polyphenylene ether)

[0183] The polyphenylene ether (A) A and the polyphenylene ether (E) B are obtained, for example, by a method comprising at least the following steps: oxidative polymerization of the monohydric phenol compound represented by the above formula (1) or (2); or oxidative polymerization of the monohydric phenol or polyhydric phenol compound represented by the above formula (1) or (8). In the above oxidative polymerization step, oxidative polymerization is preferably performed on a raw material containing at least the phenol of the above formula (1) and the phenol of the formula (2), or the phenol of the above formula (1) and the phenol of the formula (8).

[0184] Examples of the monovalent phenol compound represented by the formula (1) include 2,6-dimethylphenol, 2-methyl-6-ethylphenol, 2,6-diethylphenol, 2-ethyl-6-n-propylphenol, 2-methyl-6-chlorophenol, 2-methyl-6-bromophenol, 2-methyl-6-n-propylphenol, 2-ethyl-6-bromophenol, 2-methyl-6-n-butylphenol, 2,6-di-n-propylphenol, 2- Ethyl-6-chlorophenol, 2-methyl-6-phenylphenol, 2,6-diphenylphenol, 2-methyl-6-cresylphenol, 2,6-xylylphenol, 2,3,6-trimethylphenol, 2,3-diethyl-6-n-propylphenol, 2,3,6-tributylphenol, 2,6-di-n-butyl-3-methylphenol, 2,6-dimethyl-3-n-butylphenol, 2,6-dimethyl-3-tert-butylphenol, etc. Among them, 2,6-dimethylphenol, 2,3,6-trimethylphenol, and 2,6-diphenylphenol are particularly preferred because of their low cost and easy availability.

[0185] The monohydric phenol compound represented by the above formula (1) may be used alone or in combination of two or more.

[0186] Examples of the monovalent phenol compound represented by the formula (2) include 2-isopropyl-5-methylphenol, 2-cyclohexyl-5-methylphenol, 2-tert-butyl-5-methylphenol, 2-isobutyl-5-methylphenol, etc. From the viewpoint of suppressing multi-branching and gelation, 2-tert-butyl-5-methylphenol and 2-cyclohexyl-5-methylphenol, which are bulky substituents, are more preferred.

[0187] The monohydric phenol compound represented by the above formula (2) may be used alone or in combination of two or more.

[0188] Among the polyphenol compounds represented by the above formula (8), examples of the phenol compound having two phenol units in the molecule include 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 4,4'-methylenebis(2,6-dimethylphenol), bis(4-hydroxy-3-methylphenyl)sulfide, bis(4-hydroxy-3,5-dimethylphenyl)sulfone, α,α'-bis(4-hydroxy-3,5-dimethylphenyl)-1,4-diisopropylbenzene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, and 1,1-bis(2-methyl-4-hydroxy-5-tert-butylphenyl)butane. Among them, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane and 1,1-bis(2-methyl-4-hydroxy-5-tert-butylphenyl)butane are particularly preferred because of their low cost and easy availability.

[0189] In addition, among the polyphenol compounds represented by the above formula (8), examples of phenol compounds having three or more phenol units in the molecule include 4,4'-[(3-hydroxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[(3-hydroxyphenyl)methylene]bis(2,3,6-trimethylphenol), 4,4'-[(4-hydroxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[(4-hydroxyphenyl)methylene]bis(2,3,6-trimethylphenol), 4,4'-[(2-hydroxy-3-methoxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[(4-hydroxyphenyl)methylene]bis(2,3,6-trimethylphenol), 4,4'-[(3,4-dihydroxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[(3,4-dihydroxyphenyl)methylene]bis(2,3,6-trimethylphenol), 2,2'-[(4-hydroxyphenyl)methylene]bis(3,5,6-trimethylphenol), 4,4'-[4-(4-hydroxyphenyl)cyclohexylidene]bis(2,6-dimethylphenol), 4,4'-[(2-hydroxyphenyl)methylene]-bis(2,3,6-trimethylphenol), 4,4'-[1-[4-[1-(4-hydroxy-3,5-dimethylphenyl)-1-methylethyl]phenyl]ethylidene]bis(2,6-dimethylphenol), 4,4'-[1-[4-[1-(4 bis(2,6-dimethylphenol), 2,6-bis[(4-hydroxy-3,5-dimethylphenyl)ethyl]-4-methylphenol, 2,6-bis[(4-hydroxy-2,3,6-trimethylphenyl)methyl]-4-methylphenol, 2,6-bis[(4-hydroxy-3,5,6-trimethylphenyl)methyl]-4-ethylphenol, 2,4-bis[(4-hydroxy-3-methylphenyl)methyl]-6-methylphenol, 2,6-bis[(4-hydroxy-3-methylphenyl)methyl]-4-methylphenol, 2,4-bis[(4-hydroxy-3-cyclohexylphenyl)methyl]-6-methylphenol, 2,4-bis[(4-hydroxy-3-methylphenyl)methyl]- phenyl)methyl]-6-cyclohexylphenol, 2,4-bis[(2-hydroxy-5-methylphenyl)methyl]-6-cyclohexylphenol, 2,4-bis[(4-hydroxy-2,3,6-trimethylphenyl)methyl]-6-cyclohexylphenol, 3,6-bis[(4-hydroxy-3,5-dimethylphenyl)methyl]-1,2-benzenediol, 4,6-bis[(4-hydroxy-3,5-dimethylphenyl)methyl]-1,3-benzenediol, 2,4,6-tris[(4-hydroxy-3,5-dimethylphenyl)methyl]-1,3-benzenediol, 2,4,6-tris[(2-hydroxy-3,5-dimethylphenyl)methyl]-1,3-benzenediol, 2,2'-methylenebis[6-[(4 / 2-hydroxy-2,5 / 3,6-dimethylphenyl)methyl]-4-methylphenol], 2,2'-methylenebis[6-[(4-hydroxy-3,5-dimethylphenyl)methyl]-4-methylphenol], 2,2'-methylenebis[6-[(4 / 2-hydroxy-2,3,5 / 3,4,6-trimethylphenyl)methyl]-4-methylphenol], 2,2'-methylenebis[6-[(4-hydroxy-2,3,5-trimethylphenyl)methyl]-4-methylphenol], 4, 4'-Methylenebis[2-[(2,4-dihydroxyphenyl)methyl]-6-methylphenol], 4,4'-Methylenebis[2-[(2,4-dihydroxyphenyl)methyl]-3,6-dimethylphenol], 4,4'-Methylenebis[2-[(2,4-dihydroxy-3-methylphenyl)methyl]-3,6-dimethylphenol], 4,4'-Methylenebis[2-[(2,3,4-trihydroxyphenyl)methyl]-3,6-dimethylphenol], 6,6'-methylenebis[4-[(4-hydroxy-3,5-dimethylphenyl)methyl]-1,2,3-benzenetriol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(2-hydroxy-5-methylphenyl)methyl]phenol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(4-hydroxy-3,5-dimethylphenyl)methyl]phenol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(4-hydroxy-2-methyl- 5-cyclohexylphenyl)methyl]phenol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(2,3,4-trihydroxyphenyl)methyl]phenol], 4,4',4",4"'-(1,2-ethyldiylidene)tetrakis(2,6-dimethylphenol), 4,4',4",4"'-(1,4-phenylenedimethylene)tetrakis(2,6-dimethylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, etc. Among them, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane is particularly preferred due to its low cost and easy availability.

[0190] The polyhydric phenol compound represented by the above formula (8) may be used alone or in combination of two or more.

[0191] The number of phenolic hydroxyl groups in the polyphenol compound represented by the above formula (8) is not particularly limited as long as it is 2 to 6, but is preferably 2 to 4 from the viewpoint of easier control of the thermal curing rate.

[0192] Generally, since the oxidative polymerization of phenols having a hydrogen atom at the ortho position (e.g., 2-methylphenol, 2,5-dimethylphenol, 2-phenylphenol) can also form an ether bond at the ortho position, it becomes difficult to control the bonding position of the phenol compound during oxidative polymerization, resulting in a high molecular weight polymer having an average hydroxyl number of 3.5 or more per molecule, which is polymerized in a branched state and ultimately produces a gel component that is insoluble in the solvent.

[0193] On the other hand, when the phenol represented by the above formula (2) has a bulky substituent at one ortho position, even if there is a hydrogen atom at the ortho position on the opposite side, the bonding position of the phenol compound can be controlled during oxidative polymerization, and a polyphenylene ether having an average hydroxyl group of less than 3.0 per molecule can be obtained.

[0194] In addition, when the phenol represented by the above formula (2) has a bulky substituent at the ortho position on one side, when a monohydric phenol having a non-bulky substituent (such as a hydrogen atom, allyl group, methyl group, ethyl group, methoxy group, etc.) at the ortho position of the oxygen atom of phenol is used as the third component, a polyphenylene ether that does not undergo gelation and has an average hydroxyl group of less than 3.0 per molecule can be obtained.

[0195] In addition, the molecular weight of the polyphenylene ether can be adjusted by, for example, the molar ratio of the structure of the formula (2) to the total of the structure of the formula (1) and the structure of the formula (2), or the molar ratio of the structure of the formula (8) to the total of the structure of the formula (1) and the structure of the formula (8). That is, when the molar ratio of the structure of the formula (2) or the formula (8) is high, the molecular weight (reduced viscosity) achieved can be lowered, and when the molar ratio of the structure of the formula (2) or the formula (8) is low, the molecular weight (reduced viscosity) can be adjusted to be higher.

[0196] Here, in the method for producing polyphenylene ether, in the oxidative polymerization step, an aromatic solvent that is a good solvent for polyphenylene ether can be used as a polymerization solvent.

[0197] Here, in the method for producing polyphenylene ether according to the present embodiment, an aromatic solvent that is a good solvent for polyphenylene ether can be used as a polymerization solvent in the oxidative polymerization step.

[0198] The good solvent of the above-mentioned polyphenylene ether refers to a solvent that can dissolve polyphenylene ether. If such a solvent is given as an example, it can be cited as aromatic hydrocarbons such as benzene, toluene, xylene (including isomers of o-xylene, m-xylene, and p-xylene), ethylbenzene; halogenated hydrocarbons such as chlorobenzene and dichlorobenzene; nitro compounds such as nitrobenzene; and the like.

[0199] It should be noted that, as the polymerization catalyst used in the method for producing the polyphenylene ether in the present embodiment, a known catalyst system that can be generally used in the production of polyphenylene ether can be used. As a generally known catalyst system, a catalyst system consisting of a transition metal ion having redox ability and an amine compound that can form a complex with the transition metal ion is known, for example, a catalyst system consisting of a copper compound and an amine compound, a catalyst system consisting of a manganese compound and an amine compound, a catalyst system consisting of a cobalt compound and an amine compound, etc. Since the polymerization reaction is effectively carried out under slightly alkaline conditions, a small amount of alkali can also be added thereto or an amine compound can be further added.

[0200] The polymerization catalyst preferably used is a catalyst composed of a copper compound, a halide, and an amine compound as catalyst components, and more preferably a catalyst containing a diamine compound represented by the following formula (14) as the amine compound.

[0201] [Chemistry 22]

[0202]

[0203] (In the above formula (14), R 14 , R 15 , R 16 , R 17 Each of R is independently a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms, but not all of them are hydrogen atoms at the same time. 18 It is a linear or methyl-branched alkylene group having 2 to 5 carbon atoms.

[0204] Examples of copper compounds of the above-mentioned catalyst components are listed here. As suitable copper compounds, monovalent copper compounds, divalent copper compounds or mixtures thereof can be used. As divalent copper compounds, for example, cupric chloride, cupric bromide, copper sulfate, copper nitrate, etc. can be exemplified. In addition, as monovalent copper compounds, for example, cuprous chloride, cuprous bromide, cuprous sulfate, cuprous nitrate, etc. can be exemplified. Among these, particularly preferred metal compounds are cuprous chloride, cupric chloride, cupric bromide, cupric bromide. In addition, these copper salts can also be synthesized by oxides (such as cuprous oxide), carbonates, hydroxides, etc. and corresponding halogens or acids when used. A frequently used method is the method of mixing cuprous oxide with hydrogen halide (or a solution of hydrogen halide) as exemplified above to make.

[0205] As the above-mentioned halide, for example, hydrogen chloride, hydrogen bromide, hydrogen iodide, sodium chloride, sodium bromide, sodium iodide, potassium chloride, potassium bromide, potassium iodide, tetramethylammonium chloride, tetramethylammonium bromide, tetramethylammonium iodide, tetraethylammonium chloride, tetraethylammonium bromide, tetraethylammonium iodide, etc. In addition, they can be used in the form of an aqueous solution or a solution using a suitable solvent. These halides can be used alone as a component, or two or more can be used in combination. Preferred halides are aqueous solutions of hydrogen chloride and aqueous solutions of hydrogen bromide.

[0206] The amount of these compounds used is not particularly limited, but is preferably 2 to 20 times the molar amount of copper atoms in terms of halogen atoms. The preferred amount of copper atoms used is in the range of 0.02 to 0.6 mol per 100 mol of the phenol compound added to the polymerization reaction.

[0207] Examples of the diamine compound as the catalyst component include N,N,N',N'-tetramethylethylenediamine, N,N,N'-trimethylethylenediamine, N,N'-dimethylethylenediamine, N,N-dimethylethylenediamine, N-methylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N'-triethylethylenediamine, N,N'-diethylethylenediamine, N,N-diethylethylenediamine, N-ethylethylenediamine, N,N-dimethyl-N'-ethylethylenediamine, N,N'-dimethyl-N-ethylethylenediamine, N-n-propylethylenediamine, N,N'-n-propylethylenediamine, N-isopropylethylenediamine, N,N'-isopropylethylenediamine, N-n-butylethylenediamine, N,N' -n-butylethylenediamine, N-isobutylethylenediamine, N,N'-isobutylethylenediamine, N-tert-butylethylenediamine, N,N'-tert-butylethylenediamine, N,N,N',N'-tetramethyl-1,3-diaminopropane, N,N,N'-trimethyl-1,3-diaminopropane, N,N'-dimethyl-1,3-diaminopropane, N-methyl-1,3-diaminopropane, N,N,N',N'-tetramethyl-1,3-diamino-1-methylpropane, N,N,N',N'-tetramethyl-1,3-diamino-2-methylpropane, N,N,N',N'-tetramethyl-1,4-diaminobutane, N,N,N',N'-tetramethyl-1,5-diaminopentane, etc. Preferred diamine compounds in this embodiment are diamine compounds in which the number of carbon atoms of the alkylene group connecting two nitrogen atoms is 2 or 3. The amount of these diamine compounds used is not particularly limited, but is preferably in the range of 0.01 mol to 10 mol relative to 100 mol of the phenol compound added in the polymerization reaction.

[0208] In addition, as constituent components of the polymerization catalyst, primary amines and secondary monoamines may be included. Examples of secondary monoamines include, but are not limited to, dimethylamine, diethylamine, di-n-propylamine, diisopropylamine, di-n-butylamine, diisobutylamine, di-tert-butylamine, diamylamines, dihexylamines, dioctylamines, didecylamines, dibenzylamines, methylethylamine, methylpropylamine, methylbutylamine, cyclohexylamine, N-phenylmethanolamine, N-phenylethanolamine, N-phenylpropanolamine, N-(m-methylphenyl)ethanolamine, N-(p-methylphenyl)ethanolamine, N-(2',6'-dimethylphenyl)ethanolamine, N-(p-chlorophenyl)ethanolamine, N-ethylaniline, N-butylaniline, N-methyl-2-methylaniline, N-methyl-2,6-dimethylaniline, diphenylamine, and the like.

[0209] As a constituent component of the above-mentioned polymerization catalyst, a tertiary monoamine compound may also be included. The tertiary monoamine compound refers to an aliphatic tertiary amine including an alicyclic tertiary amine. For example, trimethylamine, triethylamine, tripropylamine, tributylamine, triisobutylamine, dimethylethylamine, dimethylpropylamine, allyldiethylamine, dimethyl-n-butylamine, diethylisopropylamine, N-methylcyclohexylamine, etc. may be cited. These tertiary monoamines may be used alone or in combination of two or more. Their usage is not particularly limited, and is preferably in the range of 15 moles or less relative to 100 moles of the phenol compound added in the polymerization reaction.

[0210] It should be noted that in the present embodiment, there is no limitation on adding a surfactant known to have an effect of improving polymerization activity. Examples of such surfactants include trioctylmethylammonium chloride known by the trade names Aliquat 336 and Capriquat.

[0211] As the oxygen-containing gas in the above-mentioned polymerization, in addition to pure oxygen, a gas obtained by mixing oxygen and an inert gas such as nitrogen in any ratio, air, and a gas obtained by mixing air and an inert gas such as nitrogen in any ratio, etc. can also be used. The pressure in the system during the polymerization reaction is sufficient to be normal pressure, but reduced pressure or increased pressure can also be used as required.

[0212] The polymerization temperature is not particularly limited, but if the temperature is too low, the reaction is unlikely to proceed, and if the temperature is too high, the reaction selectivity may decrease and gel may be generated. Therefore, the temperature is in the range of 0 to 60°C, preferably 10 to 40°C.

[0213] In the method for producing polyphenylene ether, polymerization may be performed in a poor solvent such as alcohol.

[0214] In addition, in the manufacturing method of polyphenylene ether, there is no particular restriction on the post-treatment method after the polymerization reaction is completed. Usually, an acid such as hydrochloric acid or acetic acid, or ethylenediaminetetraacetic acid (EDTA) and its salts, nitrilotriacetic acid and its salts, etc. are added to the reaction solution to deactivate the catalyst. In addition, the method for removing the by-product of the dihydric phenol body produced by the polymerization of polyphenylene ether can also be carried out using an existing known method. If the metal ion as the catalyst is in a substantially deactivated state as described above, decolorization is performed only by heating the mixture. In addition, it can also be a method of adding a necessary amount of a known reducing agent. As a known reducing agent, hydroquinone, sodium dithionite, etc. can be cited.

[0215] In the method for producing polyphenylene ether, in order to extract the compound after the copper catalyst is deactivated, water may be added, and liquid-liquid separation may be performed to separate the organic phase and the aqueous phase, and then the aqueous phase may be removed, thereby removing the copper catalyst from the organic phase. The liquid-liquid separation step is not particularly limited, and methods such as static separation and separation using a centrifuge may be cited. In order to promote the above-mentioned liquid-liquid separation, a known surfactant may be used.

[0216] Next, in the method for producing the polyphenylene ether of the present embodiment, the solvent in the organic phase containing the polyphenylene ether after liquid-liquid separation may be volatilized to perform concentration and drying.

[0217] The method for volatilizing the solvent contained in the organic phase is not particularly limited, and examples thereof include: a method of transferring the organic phase to a high-temperature concentration tank to distill off the solvent for concentration; a method of distilling off toluene for concentration using a rotary evaporator or the like; and the like.

[0218] The drying temperature in the drying step is preferably at least 60° C., more preferably 80° C., further preferably 120° C., and most preferably 140° C. If the polyphenylene ether is dried at a temperature of 60° C. or higher, the content of high-boiling-point volatile components in the polyphenylene ether powder can be effectively reduced.

[0219] In order to efficiently obtain the above-mentioned polyphenylene ether, a method of increasing the drying temperature, a method of increasing the vacuum degree in the drying atmosphere, a method of stirring during drying, etc. are effective. In particular, from the aspect of manufacturing efficiency, a method of increasing the drying temperature is preferred. The drying process preferably uses a drying machine with a mixing function. As the mixing function, a stirring type, a rotary type drying machine, etc. can be cited. This can increase the processing capacity and maintain high productivity.

[0220] In addition, the resin composition of the present embodiment comprises the above-mentioned polyphenylene ether, triallyl isocyanurate and / or triallyl cyanurate, and an organic peroxide, and may further comprise a cross-linking agent, a thermoplastic resin, a flame retardant, other additives, a solvent, etc. other than triallyl isocyanurate and triallyl cyanurate as desired. The constituent elements of the resin composition of the present embodiment are described below.

[0221] (Mass ratio of polyphenylene ether A to polyphenylene ether B)

[0222] In the present embodiment, the mass ratio (A:E) of the polyphenylene ether (A) to the polyphenylene ether (E) B is preferably 80:20 to 20:80, more preferably 80:20 to 30:70, and most preferably 70:30 to 30:70.

[0223] In the case of the above-mentioned preferred mass ratio, the cured product tends to have particularly excellent low dielectric properties, copper foil peel strength, and toluene resistance compared to a resin composition using each polyphenylene ether alone.

[0224] (Triallyl isocyanurate and / or triallyl cyanurate)

[0225] The resin composition of the present embodiment contains (B) triallyl isocyanurate and / or triallyl cyanurate as a crosslinking agent that has the ability to initiate or accelerate a crosslinking reaction.

[0226] From the viewpoint of the compatibility of triallyl isocyanurate and / or triallyl cyanurate with polyphenylene ether A and polyphenylene ether B, the coating property of the resin composition, and the characteristics of the mounted electronic circuit board being more excellent, the mass ratio of the above-mentioned (A) polyphenylene ether A and the above-mentioned (E) polyphenylene ether B to triallyl isocyanurate and / or triallyl cyanurate (total mass of polyphenylene ether A+polyphenylene ether B:total mass of triallyl isocyanurate and / or triallyl cyanurate) is preferably 90:10 to 60:40, more preferably 80:20 to 70:30.

[0227] (Crosslinking agents other than triallyl isocyanurate and triallyl cyanurate)

[0228] The resin composition of the present embodiment may contain a cross-linking agent (B') other than triallyl isocyanurate and triallyl cyanurate (hereinafter sometimes referred to as "cross-linking agent") having the ability to cause or promote a cross-linking reaction. The number average molecular weight of the above cross-linking agent is preferably 4,000 or less. If the number average molecular weight of the cross-linking agent is 4,000 or less, the increase in the viscosity of the resin composition can be suppressed, and good resin fluidity during heat molding can be obtained. The number average molecular weight can be a value measured using a conventional molecular weight determination method, specifically, a value measured using GPC, etc. can be cited.

[0229] In addition, among the above-mentioned crosslinking agents, it is preferred that an average of two or more carbon-carbon unsaturated double bonds are present in one molecule from the perspective of the crosslinking reaction. The crosslinking agent may be composed of one compound or two or more compounds. The so-called "carbon-carbon unsaturated double bond" in this specification refers to a double bond located at the end branching from the main chain when the crosslinking agent is a polymer or oligomer. As an example of a carbon-carbon unsaturated double bond, a 1,2-vinyl bond in polybutadiene can be cited.

[0230] When the number average molecular weight of the crosslinking agent is less than 600, the number (average value) of carbon-carbon unsaturated double bonds per molecule of the crosslinking agent is preferably 2 to 4. When the number average molecular weight of the crosslinking agent is 600 or more and less than 1,500, the number (average value) of carbon-carbon unsaturated double bonds per molecule of the crosslinking agent is preferably 4 to 26. When the number average molecular weight of the crosslinking agent is 1,500 or more and less than 4,000, the number (average value) of carbon-carbon unsaturated double bonds per molecule of the crosslinking agent is preferably 26 to 60. When the number average molecular weight of the crosslinking agent is within the above range, by making the number of carbon-carbon unsaturated double bonds greater than the above specific value, the reactivity of the crosslinking agent of the resin composition of the present embodiment is further improved, and the crosslinking density of the cured product of the resin composition is further improved, and as a result, more excellent heat resistance can be imparted. On the other hand, when the number average molecular weight of the crosslinking agent is within the above range, by making the number of carbon-carbon unsaturated double bonds less than the above specific value, more excellent resin fluidity can be imparted during heat molding.

[0231] Examples of the crosslinking agent include a polyfunctional methacrylate compound having two or more methacryloyl groups in the molecule, a polyfunctional acrylate compound having two or more acryloyl groups in the molecule, a polyfunctional vinyl compound having two or more vinyl groups in the molecule such as polybutadiene, a vinylbenzyl compound such as divinylbenzene having a vinylbenzyl group in the molecule, a polyfunctional maleimide compound having two or more maleimide groups in the molecule such as 4,4'-bismaleimidodiphenylmethane, a polyfunctional acrylate having two or more acryloyl groups in the molecule such as tricyclodecane dimethanol diacrylate, a polyfunctional methacrylate having two or more acryloyl groups or methacryloyl groups in the molecule such as tricyclodecane dimethanol dimethacrylate, and the like.

[0232] These cross-linking agents can be used alone or in combination of two or more. The cross-linking agent needs to include at least one compound selected from triallyl isocyanurate and triallyl cyanurate. By making the cross-linking agent include at least one compound selected from triallyl isocyanurate and triallyl cyanurate, the resin composition has a tendency to further improve the compatibility and coating properties of the cross-linking agent and the polyphenylene ether, and to have more excellent substrate properties when mounted on an electronic circuit substrate.

[0233] In addition, in the resin composition of the present embodiment, from the perspective of better compatibility between the components, the coating properties of the resin composition, and the characteristics of the mounted electronic circuit board, the total content of the (A) polyphenylene ether A and the (E) polyphenylene ether B is preferably 40% by weight or more and 80% by weight or less, more preferably 45% by weight or more and 80% by weight or less, and further preferably 50% by weight or more and 80% by weight or less, relative to 100 parts by weight of the total amount of the (A) polyphenylene ether A and the (E) polyphenylene ether B, the (B) triallyl isocyanurate and / or triallyl cyanurate, and the polyfunctional methacrylic compound.

[0234] (Organic Peroxide)

[0235] In the resin composition of the present embodiment, in addition to the above-mentioned polyphenylene ether, triallyl isocyanurate and / or triallyl cyanurate, and optionally a crosslinking agent other than triallyl isocyanurate and triallyl cyanurate, an optional (C) organic peroxide having the ability to promote the polymerization reaction may be used.

[0236] Examples of the organic peroxide include benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, di-tert-butyl peroxide, tert-butylcumyl peroxide, di(2-tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, dicumyl peroxide, di-tert-butylperoxyisophthalate, tert-butyl peroxybenzoate, 2,2-bis(tert-butylperoxy)butane, 2,2-bis(tert-butylperoxy)octane, 2,5-dimethyl-2,5-di(benzoylperoxide)hexane, bis(trimethylsilyl)peroxide, and trimethylsilyltriphenylsilyl peroxide. It should be noted that free radical initiators such as 2,3-dimethyl-2,3-diphenylbutane can also be used as reaction initiators for resin compositions. Among them, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, di(2-tert-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane are preferred from the perspective of excellent heat resistance and mechanical properties obtained and the ability to provide a cured product with a low dielectric loss tangent (and preferably a low dielectric constant).

[0237] The one-minute half-life temperature of the organic peroxide is preferably 155 to 195° C., more preferably 160 to 195° C., and further preferably 165 to 195° C. In the present specification, the one-minute half-life temperature is a temperature at which the organic peroxide decomposes and the amount of active oxygen reaches half in one minute. The one-minute half-life temperature is a value confirmed by dissolving the organic peroxide in a solvent inert to free radicals (e.g., benzene) in a concentration of 0.05 to 0.1 mol / L and thermally decomposing the organic peroxide solution under a nitrogen atmosphere.

[0238] By setting the one-minute half-life temperature of the organic peroxide to be 155° C. or higher, when the resin composition containing the polyphenylene ether is subjected to heat and pressure molding, the reaction with the crosslinking agent is initiated after the polyphenylene ether is fully melted, thereby having a tendency to have excellent moldability. On the other hand, by setting the one-minute half-life temperature of the organic peroxide to be 195° C. or lower, the decomposition rate of the organic peroxide is sufficient under normal heat and pressure molding conditions (e.g., a maximum reaching temperature of 200° C.), so the crosslinking reaction with the crosslinking agent can be effectively and slowly performed, thereby forming a cured product having good electrical properties (particularly dielectric loss tangent).

[0239] Examples of the organic peroxide having a one-minute half-life temperature in the range of 155 to 195° C. include tert-hexyl peroxyisopropyl monocarbonate (155.0° C.), tert-butyl peroxy-3,5,5-trimethylhexanoate (166.0° C.), tert-butyl peroxylaurate (159.4° C.), tert-butyl peroxyisopropyl monocarbonate (158.8° C.), tert-butyl peroxy-2-ethylhexyl monocarbonate (161.4° C.), tert-hexyl peroxybenzoate (160.3° C.), 2,5-dimethyl-2,5-di(benzoylperoxide)hexane (158.2° C.), tert-butyl peroxyacetate (159.9° C.), and tert-butyl peroxyacetate (159.9° C.). ℃), 2,2-di(tert-butylperoxy)butane (159.9℃), tert-butyl peroxybenzoate (166.8℃), 4,4-di(tert-butylperoxy)butyl valerate (172.5℃), di(2-tert-butylperoxyisopropyl)benzene (175.4℃), dicumyl peroxide (175.2℃), di-tert-hexyl peroxide (176.7℃), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (179.8℃), 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-yne (194.3℃) and tert-butylcumyl peroxide (173.3℃), etc.

[0240] The content of the organic peroxide is preferably 0.05 parts by mass or more, more preferably 0.5 parts by mass or more, further preferably 1.0 parts by mass or more, and particularly preferably 1.5 parts by mass or more, relative to 100 parts by mass of the total of the polyphenylene ether and the crosslinking agent (including triallyl isocyanurate and triallyl cyanurate), from the aspect of being able to improve the reaction rate. In addition, from the aspect of being able to suppress the dielectric constant and dielectric loss tangent of the obtained cured product to be low, the content of the organic peroxide is preferably 10 parts by mass or less, more preferably 5.0 parts by mass or less, and further preferably 4.5 parts by mass or less, relative to 100 parts by mass of the total of the polyphenylene ether and the crosslinking agent.

[0241] In addition, relative to 100 parts by mass of the cross-linking agent, the content of the organic peroxide is preferably 0.1 parts by mass or more and 50 parts by mass or less, more preferably 1.0 parts by mass or more and 25 parts by mass or less, further preferably 2.0 parts by mass or more and 22.5 parts by mass or less, further more preferably 3.0 parts by mass or more and 21.5 parts by mass or less, and particularly preferably greater than 5.0 parts by mass and less than 20 parts by mass. By making the content 0.1 parts by mass or more, there is a tendency to increase the reaction rate, and by making the content 50 parts by mass or less, there is a tendency to suppress the dielectric constant and dielectric loss tangent of the obtained cured product to be low.

[0242] In addition, relative to 100 parts by mass of the total mass of triallyl isocyanurate and / or triallyl cyanurate, the content of the organic peroxide is preferably 0.1 parts by mass or more and 50 parts by mass or less, more preferably 1.0 parts by mass or more and 25 parts by mass or less, further preferably 2.0 parts by mass or more and 22.5 parts by mass or less, further more preferably 3.0 parts by mass or more and 21.5 parts by mass or less, and particularly preferably greater than 5.0 parts by mass and less than 20 parts by mass. By making the content 0.1 parts by mass or more, there is a tendency to increase the reaction rate, and by making the content 50 parts by mass or less, there is a tendency to suppress the dielectric constant and dielectric loss tangent of the obtained cured product to be low.

[0243] (Multifunctional methacrylic compound)

[0244] The resin composition of this embodiment preferably further contains (D) a polyfunctional methacrylic compound in addition to the above-mentioned components (A), (B), (B'), and (C), because the dielectric properties, heat resistance, and solvent resistance of the resin composition and its cured product can be improved.

[0245] Here, the above-mentioned multifunctional methacrylic compound is not particularly limited as long as it has an average of more than one methacryloyl functional group in one molecule. From the perspective of cross-linking reaction, it is preferably an average of more than two methacryloyl functional groups in one molecule. It may be composed of one compound or two or more compounds.

[0246] Examples of the polyfunctional methacrylic compound include tricyclodecane dimethanol dimethacrylate (DCP), trimethylolpropane trimethacrylate (TMPT), ethoxylated bisphenol A dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, and neopentyl glycol dimethacrylate.

[0247] In addition, among these, from the aspect of excellent compatibility with polyphenylene ether, it is preferred to include at least one compound selected from tricyclodecane dimethanol dimethacrylate (DCP) and trimethylolpropane trimethacrylate (TMPT). By further adding these multifunctional methacrylic compounds, the dielectric properties, heat resistance and solvent resistance of the resin composition and its cured product can be further improved.

[0248] From the viewpoint of reducing the viscosity of the varnish in the step of mixing the resin composition with the solvent to improve the handling properties, and reducing the melt viscosity of the resin composition in the thermal curing step to increase the crosslinking reaction rate, the polyfunctional methacrylic compound preferably has a molecular weight of less than 1000, more preferably less than 800, and even more preferably less than 500. By using a low molecular weight polyfunctional methacrylic compound, a resin composition and a cured product thereof having excellent electrical properties, heat resistance, and solvent resistance can be obtained in the present embodiment.

[0249] Furthermore, in the resin composition of the present embodiment, from the perspective of further improving the dielectric properties, heat resistance, and solvent resistance of the resin composition and the cured product, the content of the (D) polyfunctional methacrylic compound is preferably 20% by weight to 80% by weight, more preferably 25% by weight to 75% by weight, and even more preferably 30% by weight to 70% by weight, relative to 100 parts by weight of the total amount of the (B) triallyl isocyanurate and / or triallyl cyanurate and the (D) polyfunctional methacrylic compound.

[0250] In the case of containing (B') a cross-linking agent other than triallyl isocyanurate and triallyl cyanurate, in the resin composition of the present embodiment, the content of the above-mentioned (A) polyphenylene ether A and the above-mentioned (E) polyphenylene ether B is preferably 40% by weight or more and 80% by weight or less, more preferably 45% by weight or more and 80% by weight or less, and further preferably 50% by weight or more and 80% by weight or less, relative to 100 parts by weight of the total amount of the above-mentioned (A) polyphenylene ether A and the above-mentioned (E) polyphenylene ether B, the above-mentioned (B) triallyl isocyanurate and / or triallyl cyanurate, the above-mentioned (D) polyfunctional methacrylic compound, and (B') other cross-linking agents, from the viewpoint of better compatibility between the cross-linking agent and the polyphenylene ether, the coating property of the resin composition, and the characteristics of the mounted electronic circuit board.

[0251] (Thermoplastic resin)

[0252] The resin composition of the present embodiment may further contain a thermoplastic resin.

[0253] The thermoplastic resin is preferably at least one selected from the group consisting of a block copolymer of a vinyl aromatic compound and an olefin-based olefin compound and its hydride (a hydrogenated block copolymer obtained by hydrogenating a block copolymer of a vinyl aromatic compound and an olefin-based olefin compound), and a homopolymer of a vinyl aromatic compound. The content of the unit from the vinyl aromatic compound in the block copolymer or its hydride is preferably 20% by mass or more, more preferably 22% by mass or more, and can be 99% by mass or less. By making the content of the unit from the vinyl aromatic compound in the block copolymer or its hydride 20% by mass or more, there is a tendency to further improve the compatibility with polyphenylene ether and further improve the adhesion strength with the metal foil.

[0254] As the above-mentioned vinyl aromatic compound, any one having an aromatic ring and a vinyl group in the molecule may be used, and examples thereof include styrene, etc. As the chain olefin-based olefin compound, any one having a straight-chain or branched-chain structure in the molecule may be used, and examples thereof include ethylene, propylene, butylene, isobutylene, butadiene, and isoprene, etc. Among these, the thermoplastic resin is preferably at least one selected from the group consisting of styrene-butadiene block copolymers, styrene-ethylene-butadiene block copolymers, styrene-ethylene-butylene block copolymers, styrene-butadiene-butylene block copolymers, styrene-isoprene block copolymers, styrene-ethylene-propylene block copolymers, styrene-isobutylene block copolymers, hydrogenated products of styrene-butadiene block copolymers, hydrogenated products of styrene-ethylene-butadiene block copolymers, hydrogenated products of styrene-butadiene-butylene block copolymers, hydrogenated products of styrene-isoprene block copolymers, and styrene homopolymers (polystyrene) from the viewpoint of having better compatibility with polyphenylene ether. More preferably, it is at least one selected from the group consisting of styrene-butadiene block copolymers, hydrogenated products of styrene-butadiene block copolymers, and polystyrene.

[0255] The hydrogenation rate in the hydrogenated product is not particularly limited, and a portion of the carbon-carbon unsaturated double bonds derived from the alkene-based olefin compound may remain.

[0256] The weight average molecular weight of the thermoplastic resin is preferably 10,000 to 300,000, more preferably 20,000 to 290,000, and further preferably 30,000 to 280,000. By making the weight average molecular weight 10,000 or more, the resin composition of the present embodiment has a tendency to have better heat resistance when cured. By making the weight average molecular weight 300,000 or less, the resin composition of the present embodiment has a tendency to have better resin fluidity during heat molding. The weight average molecular weight is obtained by the method described in the examples described later.

[0257] Based on 100 parts by mass of the total of polyphenylene ether and the cross-linking agent, the content of the above-mentioned thermoplastic resin is preferably 2 to 20 parts by mass, more preferably 3 to 19 parts by mass, further preferably 4 to 18 parts by mass, and particularly preferably 5 to 17 parts by mass. By making the content 2 parts by mass or more, the resin composition of the present embodiment has a tendency to have a low dielectric constant, a low dielectric loss tangent, and a better adhesion to the metal foil when cured. By making the content 20 parts by mass or less, the resin composition of the present embodiment has a tendency to have a better resin fluidity during heat molding. In addition, from the same aspect, based on 100 parts by mass of the total of polyphenylene ether and the cross-linking agent, the content of the thermoplastic resin is preferably 2 to 20 parts by mass, more preferably 3 to 19 parts by mass.

[0258] In addition, the resin composition of this embodiment may contain thermoplastic resins other than the thermoplastic resins having the types and weight average molecular weights described above.

[0259] (Flame Retardant)

[0260] The resin composition of the present embodiment preferably further contains a flame retardant.

[0261] As the above-mentioned flame retardant, from the aspect of being able to improve heat resistance, there is no particular restriction as long as it is incompatible with other components contained in the resin composition after the resin composition is cured. It is preferred that the flame retardant is incompatible with the polyphenylene ether and / or crosslinking agent in the resin composition after the resin composition is cured. As a flame retardant, for example, inorganic flame retardants such as antimony trioxide, aluminum hydroxide, magnesium hydroxide, and zinc borate; aromatic bromine compounds such as hexabromobenzene, decabromodiphenylethane, 4,4-dibromobiphenyl, and ethylenebistetrabromophthalimide; phosphorus-based flame retardants such as resorcinol bis(diphenyl phosphate) and resorcinol bis(di(dimethylphenyl) phosphate). These flame retardants can be used alone or in combination of two or more. Among these, the flame retardant is preferably decabromodiphenylethane from the perspective of the compatibility of the flame retardant with the polyphenylene ether, the coating property of the resin composition, and the characteristics of the installed electronic circuit substrate.

[0262] The content of the flame retardant is not particularly limited, but is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 15 parts by mass or more, relative to 100 parts by mass of the total of the polyphenylene ether resin and the crosslinking agent, from the perspective of maintaining the flame retardancy of the V-0 grade of UL Standard 94. In addition, from the perspective of being able to maintain the dielectric loss tangent of the obtained cured product at a low level (preferably from the perspective of being able to further maintain the dielectric constant at a low level), the content of the flame retardant is preferably 50 parts by mass or less, more preferably 45 parts by mass or less, and further preferably 40 parts by mass or less.

[0263] (Silica filler)

[0264] The resin composition of the present embodiment may further contain a silica filler. As the silica filler, for example, natural silica, fused silica, synthetic silica, amorphous silica, AEROSIL, and hollow silica can be cited. The content of the silica filler can be 10 to 300 parts by mass relative to 100 parts by mass of the total of the polyphenylene ether and the crosslinking agent. In addition, the silica filler can be a material whose surface has been surface-treated using a silane coupling agent or the like.

[0265] The resin composition of the present embodiment may further include additives such as a heat stabilizer, an antioxidant, a UV absorber, a surfactant, a lubricant, a solvent, etc., in addition to the flame retardant and the silica filler. When the resin composition of the present embodiment includes a solvent, the resin composition may be in the form of a varnish in which the solid components in the resin composition are dissolved or dispersed in the solvent, and a resin film may be formed from the resin composition of the present embodiment.

[0266] (Solvent)

[0267] The resin composition of the present embodiment may further contain a solvent. As a solvent, from the aspect of solubility, aromatic compounds such as toluene and xylene, methyl ethyl ketone (MEK), cyclopentanone, cyclohexanone and chloroform are preferred. These solvents may be used alone or in combination of two or more.

[0268] <Resin film>

[0269] The resin film of this embodiment contains the resin composition of this embodiment.

[0270] The method for producing the film is not particularly limited, and the film can be obtained by, for example, molding the resin composition of the present embodiment into a film or sheet.

[0271] <Prepreg>

[0272] The prepreg of the present embodiment is a composite of a substrate and a resin composition of the present embodiment, and the resin composition of the present embodiment can be impregnated or coated into the substrate. The method for manufacturing the prepreg is not particularly limited, and the prepreg can be obtained, for example, by immersing the substrate in a resin composition (varnish) containing a solvent and then drying and removing the solvent component using a hot air dryer or the like.

[0273] Examples of the substrate include: various glass cloths such as roving, cloth, chopped strand mat, and surface mat; asbestos cloth, metal fiber cloth, and other synthetic or natural inorganic fiber cloths; woven fabrics or nonwoven fabrics obtained from liquid crystal fibers such as fully aromatic polyamide fibers, fully aromatic polyester fibers, and polybenzoxazole fibers; natural fiber cloths such as cotton cloth, linen, and felt; natural cellulose substrates such as carbon fiber cloth, kraft paper, cotton paper, and cloth obtained from paper-glass mixed fibers; polytetrafluoroethylene porous membranes; and the like. Glass cloth is preferred. These substrates can be used alone or in combination of two or more.

[0274] The ratio of the solid content of the resin composition (components other than the solvent of the resin composition) in the prepreg of the present embodiment is preferably 30 to 80% by mass, more preferably 40 to 70% by mass. By making the above ratio more than 30% by mass, when the prepreg is used for electronic substrate applications, there is a tendency for insulation reliability to be more excellent. By making the above ratio less than 80% by mass, there is a tendency for mechanical properties such as flexural modulus to be more excellent in applications such as electronic substrates.

[0275] <Metal-clad laminate>

[0276] The metal-clad laminate of the present embodiment can be obtained by laminating and curing the resin composition of the above-mentioned present embodiment, the resin film of the present embodiment or the prepreg of the present embodiment with metal foil. The metal-clad laminate of the present embodiment preferably has a cured product (hereinafter also referred to as "cured product composite") of a prepreg and a metal foil that is laminated and closely fitted, and can be suitably used as a material for electronic substrates. As metal foil, for example, aluminum foil and copper foil can be cited, and among these, copper foil is preferred due to its low resistance. The cured product composite combined with metal foil can be 1 sheet or multiple sheets, and metal foil is stacked on one side or both sides of the composite according to the purpose and processed into a laminate.

[0277] As a method for manufacturing the metal-clad laminate of the present embodiment, for example, the following method can be cited: forming a composite body (such as the above-mentioned prepreg) composed of a resin composition and a substrate, overlapping it with a metal foil, and then curing the resin composition to obtain a laminate formed by laminating a cured product laminate and a metal foil. One of the particularly preferred uses of the above-mentioned metal-clad laminate is a printed wiring board. In the printed wiring board, it is preferred that at least a portion of the metal foil is removed from the metal-clad laminate.

[0278] <Printed wiring board>

[0279] In the printed wiring board of the present embodiment, a part of the metal foil is removed from the metal-clad laminate of the present embodiment. The printed wiring board of the present embodiment is typically formed by a method of pressurizing and heating the prepreg of the present invention. As a substrate, the same substrate as the above-mentioned substrate for the prepreg can be cited. The printed wiring board of the present embodiment has excellent copper foil peeling strength and toluene resistance by including the resin composition of the present embodiment.

[0280] Example

[0281] The present embodiment will be described in further detail below based on examples, but the present embodiment is not limited to the following examples.

[0282] <Polyphenylene ether>

[0283] (Manufacturing Example)

[0284] Production Example 1: Polyphenylene ether 1 (PPE1)

[0285] A 40-liter jacketed polymerization kettle equipped with a nozzle for introducing oxygen-containing gas, a turbine stirring blade and a guide plate at the bottom of the polymerization kettle and a reflux cooler at the exhaust line at the top of the polymerization kettle was used. 3.6 g of divalent copper oxide, 27.1 g of a 47% by mass aqueous solution of hydrogen bromide, 8.7 g of di-tert-butylethylenediamine, 42.0 g of di-n-butylamine, 128.0 g of butyldimethylamine, 14.6 kg of toluene, 2.0 g of trioctylmethylammonium chloride (R=C8-C 10 ) to make a uniform solution. Next, a pump was used to drip 647.8 g of 2-tert-butyl-5-methylphenol, 2352.3 g of 2,6-dimethylphenol and 2.35 kg of toluene into the polymerization kettle over 35 minutes. At the same time, dry air was introduced into the polymerization solution from the bottom of the polymerization kettle at a rate of 31.5 L / min using a nozzle to initiate polymerization. Dry air was introduced for 240 minutes to obtain a polymerization mixture. It should be noted that during the polymerization, the internal temperature was controlled to 40°C. The polymerization mixture (polymerization liquid) at the end of the polymerization was in a uniform solution state.

[0286] Thereafter, the ventilation of dry air was stopped, and 38.73 g of ethylenediaminetetraacetic acid tetrasodium salt (reagent manufactured by Tongren Chemical Research Institute) was added to the polymerization mixture in the form of 2 kg of aqueous solution. The polymerization mixture was stirred at 70° C. for 240 minutes, then allowed to stand for 20 minutes, and the organic phase and the aqueous phase were separated by liquid-liquid separation. The organic phase was concentrated by a rotary evaporator until the polymer concentration reached 30% by mass.

[0287] The concentrated solution was mixed with methanol in a mass ratio of 4 to the polymer solution to precipitate the polymer. The wet polyphenylene ether was obtained by vacuum filtration using a glass filter. The wet polyphenylene ether was further washed with methanol in an amount of 4 to the mass ratio of the wet polyphenylene ether, and the washing operation was performed three times. Thereafter, the wet polyphenylene ether was kept at 140° C. and 1 mmHg for 120 minutes to obtain a dry polyphenylene ether (PPE1).

[0288] Production Example 2: Polyphenylene ether 2 (PPE2)

[0289] After the polymerization was initiated, the same operation as in Production Example 1 was carried out except that dry air was passed for 200 minutes to obtain polyphenylene ether (PPE2).

[0290] Production Example 3: Polyphenylene ether 3 (PPE3)

[0291] Polyphenylene ether (PPE3) was obtained by the same method as in Production Example 1 except that 928.3 g of 2-tert-butyl-5-methylphenol, 2071.7 g of 2,6-dimethylphenol and 2.07 kg of toluene were used as the dropping solution.

[0292] Production Example 4: Polyphenylene ether 4 (PPE4)

[0293] Polyphenylene ether (PPE4) was obtained by the same method as in Production Example 1 except that 1096.6 g of 2-tert-butyl-5-methylphenol, 1903.4 g of 2,6-dimethylphenol and 1.90 kg of toluene were used as the dropping solution.

[0294] Production Example 5: Polyphenylene ether 5 (PPE5)

[0295] Polyphenylene ether (PPE5) was obtained by the same method as in Production Example 1 except that 1417.9 g of 2-tert-butyl-5-methylphenol, 1582.1 g of 2,6-dimethylphenol and 1.58 kg of toluene were used as the dropping solution.

[0296] Production Example 6: Polyphenylene ether 6 (PPE6)

[0297] As PPE6, “XYRON S203A” manufactured by Asahi Kasei Corporation was used.

[0298] Production Example 7: Polyphenylene ether 7 (PPE7)

[0299] Polyphenylene ether (PPE7) was obtained by the same method as in Production Example 1 except that 314.0 g of 2-tert-butyl-5-methylphenol, 2686.0 g of 2,6-dimethylphenol and 2.68 kg of toluene were used as the dropping solution.

[0300] Production Example 8: Polyphenylene ether 8 (PPE8)

[0301] A 40-liter jacketed polymerization kettle equipped with a nozzle for introducing oxygen-containing gas, a turbine stirring blade and a guide plate at the bottom of the polymerization kettle, and a reflux cooler at the exhaust line at the top of the polymerization kettle, 2.4 g of divalent copper oxide, 18.1 g of a 47% by mass aqueous solution of hydrogen bromide, 5.8 g of di-tert-butylethylenediamine, 28.1 g of di-n-butylamine, 85.6 g of butyldimethylamine, 17.9 kg of toluene, and 1903.4 g of 2,6-dimethylphenol, 1096.6 g of 2-tert-butyl-5-methylphenol were added to the polymerization kettle while blowing nitrogen at a flow rate of 17.1 L / min to prepare a uniform solution. Next, dry air was introduced into the polymerization kettle at a rate of 10.5 L / min using a nozzle to initiate polymerization. Dry air was introduced for 120 minutes to obtain a polymerization mixture. It should be noted that during the polymerization, the internal temperature was controlled to 20°C. The polymerization mixture (polymerization liquid) at the end of the polymerization is in a uniform solution state.

[0302] The ventilation of dry air was stopped, and 25.9 g of ethylenediaminetetraacetic acid tetrasodium salt (reagent produced by Tongren Chemical Research Institute) was added to the polymerization mixture in the form of an aqueous solution of 2 kg of water. The polymerization mixture was stirred at 70° C. for 150 minutes, then allowed to stand for 20 minutes, and the organic phase and the aqueous phase were separated by liquid-liquid separation. The organic phase was concentrated by a rotary evaporator until the polymer concentration reached 25% by mass.

[0303] The above solution was mixed with methanol in a ratio of 6 to the polymer solution to precipitate the polymer. The wet polyphenylene ether was obtained by vacuum filtration using a glass filter. The wet polyphenylene ether was further washed with methanol in an amount of 3 to the wet polyphenylene ether. The above washing operation was performed three times. The wet polyphenylene ether was then kept at 140° C. and 1 mmHg for 120 minutes to obtain polyphenylene ether 8 (PPE8) in a dry state.

[0304] Production Example 9: Polyphenylene ether 9 (PPE9)

[0305] Polyphenylene ether 9 (PPE9) was obtained by the same method as in Production Example 1 except that 1720.3 g of 2-tert-butyl-5-methylphenol, 1279.7 g of 2,6-dimethylphenol and 2.68 kg of toluene were used as the dropping solution.

[0306] Production Example 9': Modified polyphenylene ether 9 (modified PPE9)

[0307] In a 500 mL three-necked flask equipped with a temperature regulator, a stirring device, a cooling device and a dropping funnel, 50 g of polyphenylene ether 7 (PPE7) produced by the above production method, 50 g of toluene, 10.2 g of chloromethylstyrene (the ratio of p-chloromethylstyrene to m-chloromethylstyrene is 50 / 50, manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.43 g of tetra-n-butylammonium bromide were added. The mixture was then stirred and dissolved, and the liquid temperature was set to 85° C. A sodium hydroxide aqueous solution (sodium hydroxide 7.12 g / water 7.12 g) was added dropwise to the mixed solution over 1 hour, and stirring was continued at 85° C. for 5 hours.

[0308] Next, the obtained water layer is removed using a separatory funnel to obtain a toluene layer (polymer solution) containing a polymer. The polymer is precipitated by mixing with methanol in a ratio of 10 to the polymer solution. The wet polyphenylene ether is obtained by vacuum filtration using a glass filter. The wet polyphenylene ether is further cleaned with a cleaning solvent (methanol: water = 80:20) in an amount of 2.5 relative to the wet polyphenylene ether. After the above-mentioned cleaning operation based on a methanol-water mixed solvent is performed three times, the wet polyphenylene ether is cleaned with methanol in an amount of 2.5 relative to the wet polyphenylene ether.

[0309] After the above-mentioned washing operation with methanol was performed twice, the wet polyphenylene ether was kept under conditions of 100° C. and 1 mmHg for 8 hours to obtain a dried modified polyphenylene ether 9 (modified PPE 9).

[0310] It should be noted that 1 By H NMR measurement, a proton peak derived from an olefin of the styryl group was confirmed, from which it was determined that the hydroxyl group was modified into a styryl group.

[0311] Production Example 10: Polyphenylene ether 10 (PPE10)

[0312] A 1.5-liter jacketed reactor equipped with a nozzle for introducing oxygen-containing gas, a turbine stirrer, and a baffle at the bottom of the reactor, and a reflux cooler at the exhaust line at the top of the reactor, was used. A mixture of 0.10 g of cuprous oxide and 0.77 g of 47% hydrogen bromide prepared in advance, 0.25 g of N,N'-di-tert-butylethylenediamine, 3.62 g of dimethyl-n-butylamine, 1.19 g of di-n-butylamine, 894 g of toluene, 79.45 g of 2,6-dimethylphenol, and 20.55 g of 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane were added to the reactor. Next, air was introduced into the reactor at a rate of 1.05 L / min using a nozzle while stirring vigorously, and a heat medium was circulated in the jacket to adjust the polymerization temperature to maintain 20°C. 150 minutes after the start of air introduction, the ventilation of the air was stopped, and the nitrogen in the reactor was replaced, and then 1.10 g of ethylenediaminetetraacetic acid tetrasodium salt tetrahydrate (reagent manufactured by Tongren Chemical Research Institute) was added to the polymerization mixture in the form of an aqueous solution of 100 g of water. Then, it was heated to 70°C and copper extraction was carried out at 70°C for 2 hours. Thereafter, it was separated into an unmodified polyphenylene ether solution (organic phase) and an aqueous phase with a catalyst metal transferred by static separation. The above-mentioned organic phase was concentrated by a rotary evaporator until the polymer concentration reached 25% by mass.

[0313] The above solution was mixed with methanol in a ratio of 6 to the polymer solution to precipitate the polymer. The wet polyphenylene ether was obtained by vacuum filtration using a glass filter. The wet polyphenylene ether was further washed with methanol in an amount of 3 to the wet polyphenylene ether. The above washing operation was performed three times. The wet polyphenylene ether was then kept at 140° C. and 1 mmHg for 120 minutes to obtain a dry polyphenylene ether 10 (PPE10).

[0314] ·Production Example 10': Modified polyphenylene ether 10 (modified PPE10)

[0315] A 500mL three-necked flask with a pipeline for introducing nitrogen at the top of the reactor and a reflux cooler at the exhaust line at the top of the reactor was used. After nitrogen substitution was performed inside the reactor in the three-necked flask, 20g of polyphenylene ether 8 (PPE8) and 0.25g of 4-dimethylaminopyridine produced by the above-mentioned manufacturing method were added. 5.7mL of triethylamine was added using a syringe while stirring. Thereafter, 2.0mL of methacryloyl chloride was collected into a syringe and added dropwise to the system at room temperature. After the addition was completed, the flask was heated in an oil bath for 1 hour and stirred continuously at 90°C. Thereafter, it was further heated in an oil bath and the reaction was continued under reflux. After 4 hours of reflux, the heating was stopped, and 0.66g of methanol was added after returning to room temperature to stop the reaction. The reaction solution was then filtered using a glass filter to obtain a solution of triethylammonium salt from which the by-product was removed. The above solution was mixed with methanol in a ratio of 10 to the polymer solution to precipitate the polymer. The wet polyphenylene ether was obtained by vacuum filtration using a glass filter. The wet polyphenylene ether was further washed with methanol in an amount of 2.5 relative to the wet polyphenylene ether. The above washing operation was performed three times. The wet polyphenylene ether was then kept at 100°C and 1 mmHg for 8 hours to obtain a modified polyphenylene ether 10 (modified PPE10) in a dry state. It should be noted that the 1 By H NMR measurement, a proton peak derived from an olefin of a methacryloyl group was confirmed, from which it was determined that the hydroxyl group was modified into a methacryloyl group.

[0316] Production Example 11: Polyphenylene ether 11 (PPE11)

[0317] Polyphenylene ether 11 (PPE11) was obtained by the same method as in Production Example 8 except that 71.92 g of 2,6-dimethylphenol and 28.08 g of 4,4′-dihydroxy-2,2′,3,3′,5,5′-hexamethylbiphenyl were used.

[0318] Production Example 11': Modified polyphenylene ether 11 (modified PPE11)

[0319] Modified polyphenylene ether 11 (modified PPE11) was obtained by the same method as in Production Example 9' except that polyphenylene ether 11 (PPE11) produced by the above production method was used as a raw material.

[0320] (Analysis of Polyphenylene Ether)

[0321] The following analyses were performed on each PPE obtained in the above-mentioned production examples. The analysis results are shown in Table 1.

[0322] (1) Reduced viscosity of polyphenylene ether (ηsp / c)

[0323] A 0.5 g / dL chloroform solution of polyphenylene ether was prepared, and the reduced viscosity (ηsp / c) (dL / g) at 30° C. was determined using an Ubbelohde viscometer.

[0324] (2) Number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of polyphenylene ether

[0325] As a measuring apparatus, a gel permeation chromatograph (manufactured by Shimadzu Corporation, LC-2030C Plus) was used, and a calibration curve was prepared using standard polystyrene and ethylbenzene, and the number average molecular weight (Mn) of the obtained polyphenylene ether was measured using this calibration curve. As standard polystyrene, polystyrenes with molecular weights of 3,650,000, 2,170,000, 1,090,000, 681,000, 204,000, 52,000, 30,200, 13,800, 3,360, 1,300, and 550 were used.

[0326] As for the column, a column formed by connecting two K-805L manufactured by Showa Denko K.K. in series was used. Chloroform was used as the solvent, and the flow rate of the solvent was set to 1.0 mL / min and the column temperature was set to 40° C. The measurement was performed. As a sample for measurement, a 1 g / L chloroform solution of polyphenylene ether was prepared and used. As for the wavelength of UV of the detection unit, it was 254 nm in the case of standard polystyrene and 283 nm in the case of polyphenylene ether.

[0327] Based on the measurement data, the number average molecular weight (Mn) (g / mol), the weight average molecular weight (Mw), and the molecular weight distribution (Mw / Mn) were calculated from the ratio of the peak areas based on the curve representing the molecular weight distribution obtained by GPC.

[0328] (3) Number of OH groups of polyphenylene ether

[0329] 5.0 mg of polyphenylene ether was weighed. Then, the weighed polyphenylene ether was dissolved in 25 mL of dichloromethane. 150 μL of 2% by mass tetraethylammonium hydroxide (TEAH) ethanol solution was added to 2.0 mL of the prepared solution, and then the absorbance (Abs) at 318 nm was measured using a UV spectrophotometer (Hitachi: U-3210 model) (using a dish with a dish length of 1 cm for absorbance measurement). Then, based on the measurement results, the OH base obtained from the absorbance was calculated using the following mathematical formula (1).

[0330] OH number (μmol / g) = [(25×Abs) / (ε×5)]×10 6 Mathematical formula (1)

[0331] (Here, ε represents the absorption coefficient, which is 4700 L / mol·cm.)

[0332] (4) Number of OH groups per polyphenylene ether molecule

[0333] The number of OH groups per molecule of the polyphenylene ether was determined by the following mathematical formula (2) using the number average molecular weight determined by gel permeation chromatography (described in detail in (2) above).

[0334] Average number of hydroxyl groups per molecule (number / molecule) = (number average molecular weight determined by gel permeation chromatography) × (number of OH groups determined from absorbance) / 10 6 ···Mathematical formula (2)

[0335] (5) Long-term solubility in toluene (TL solubility)

[0336] 5.0 g of polyphenylene ether and 5.0 g of toluene were weighed in a glass transparent screw tube and mixed using a stirring bar and a magnetic stirrer at 20° C. The mixed solution was checked after 1 day and judged according to the following criteria.

[0337] 0:The solution maintains transparency

[0338] △: Slightly insoluble matter

[0339] ×: Obviously insoluble or a large amount of insoluble components exist

[0340]

[0341] <Ingredients other than polyphenylene ether>

[0342] (Triallyl isocyanurate and / or triallyl cyanurate)

[0343] Triallyl isocyanurate (product name: TAIC, manufactured by Tokyo Chemical Industry Co., Ltd., number average molecular weight: 249.3, number of unsaturated double bonds in the molecule: 3)

[0344] (Organic Peroxide)

[0345] ·Bis(1-tert-butylperoxy-1-methylethyl)benzene (product name: Perbutyl P, manufactured by NOF Corporation, 1-minute half-life temperature: 175.4°C)

[0346] (Multifunctional methacrylic compound)

[0347] · Tricyclodecane dimethanol dimethacrylate (product name: DCP, manufactured by Tokyo Chemical Industry Co., Ltd., number average molecular weight: 332.4, number of methacryloyl functional groups in the molecule: 2)

[0348] · Trimethylolpropane trimethacrylate (product name: TMPT, manufactured by Tokyo Chemical Industry Co., Ltd., number average molecular weight: 338.4, number of methacryloyl functional groups in the molecule: 3)

[0349] (Thermoplastic resin)

[0350] Hydrogenated styrene-based thermoplastic resin (SEBS) (product name: Tuftec H1041, manufactured by Asahi Kasei Corporation, weight average molecular weight: about 90,000, styrene unit content: 32% by mass)

[0351] (Flame Retardant)

[0352] · Decabromodiphenylethane (Product name: SAYTEX8010, manufactured by Albemarle Corporation)

[0353] (Bulking Agent)

[0354] Spherical silicon oxide (product name: SO-C6, manufactured by Admatechs)

[0355] [Example A]

[0356] As shown below, a cured product of the resin composition of each example and comparative example was produced.

[0357] (Example 1)

[0358] According to the composition and solvent shown in Table 2, a thermoplastic resin was added to 205 parts by mass of toluene, stirred and dissolved, and then a flame retardant, spherical silica, and PPE1 synthesized by the above method were added, and stirring was continued until PPE1 was dissolved. Then, triallyl isocyanurate and an organic peroxide were added to the dissolved product, and stirred sufficiently to obtain a varnish.

[0359] After the obtained varnish was impregnated into the L glass cloth, the cloth was passed through a slit of a predetermined width to scrape off excess varnish, and dried in a drying oven at 130° C. for a predetermined time to remove toluene, thereby obtaining a prepreg.

[0360] The obtained prepreg was cut into a specified size, a specified number of sheets were stacked, and copper foil (manufactured by Furukawa Electric Co., Ltd., thickness 18 μm, F1N-WS foil) was stacked on both sides of the stacked prepreg, and vacuum pressing was performed in this state to obtain a copper-clad laminate. In the vacuum pressing step, first, 40 kg / cm 2 The temperature was raised from 30°C to 200°C at a rate of 2°C / min. After the temperature reached 200°C, a pressure of 40kg / cm 2 The mixture was maintained at 200° C. for 60 minutes under a pressure of 1.5° C.

[0361] Thereafter, the copper-clad laminate obtained was etched to remove the copper foil, thereby obtaining a laminate as a sample.

[0362] (Examples 2 to 6, Comparative Examples 1 to 4)

[0363] Except for changing the resin composition as shown in Table 2, a resin composition, a varnish, a prepreg and a copper-clad laminate were obtained under the same conditions as in Example 1.

[0364] It should be noted that, in Comparative Example 1 using PPE6 and Comparative Example 2 using PPE7, PPE was not completely dissolved in toluene, and thus a prepreg and a copper-clad laminate could not be produced.

[0365] <Evaluation>

[0366] The following evaluations were performed on each of the samples obtained in the above-mentioned Examples and Comparative Examples.

[0367] (1) Copper foil peel strength of cured product of resin composition (peel strength N / mm)

[0368] The stress when the copper foil of the copper-clad laminate is peeled off at a fixed speed is measured. The copper-clad laminate obtained in the above-mentioned embodiment and comparative example, which uses a 18μm thick copper foil (manufactured by Furukawa Electric Co., Ltd., F1N-WS foil) is cut into a size of 10mm in width × 120mm in length, and an Autograph (manufactured by Shimadzu Corporation, AG-I20kN) is used to measure the average value of the load when the copper foil is peeled off at an angle of 90° relative to the removal surface at a speed of 50mm / minute, and the average value of 3 measurements is obtained.

[0369] In addition, from the perspective of preventing wiring peeling, the calculated copper foil peel strength of the cured product of the resin composition is preferably 0.39 N / mm or more, more preferably 0.52 N / mm or more, further preferably 0.55 N / mm or more, and particularly preferably 0.60 N / mm or more.

[0370] (2) Toluene immersion test

[0371] The cured products of the resin compositions obtained in the above Examples and Comparative Examples and having a thickness of about 0.5 mm were cut into pieces having a length of 50 mm and a width of 5 mm, and immersed in a sufficient amount of toluene at 20° C. for 24 hours, and the weight reduction was evaluated according to the following criteria.

[0372] ○: When the mass reduction before and after immersion is less than 0.5 mass%

[0373] △: When the mass reduction before and after immersion is 0.5 mass% or more and less than 1 mass%

[0374] ×: When the mass reduction before and after immersion is 1 mass % or more

[0375]

[0376] As shown in Tables 1 and 2, it is understood that PPEs 1 to 4 have excellent solubility in toluene and that resin compositions excellent in copper foil peel strength and toluene resistance can be obtained by using these.

[0377] [Example B]

[0378] Cured products of the resin compositions of the respective Examples and Comparative Examples were prepared as follows.

[0379] (Example 7)

[0380] PPE1 synthesized as described above was added to 102 parts by mass of toluene according to the composition shown in Table 3, and stirred until PPE1 was dissolved. Then, triallyl isocyanurate, a polyfunctional methacrylic compound, and an organic peroxide were added, respectively, and stirred sufficiently to obtain a varnish.

[0381] After the obtained varnish was impregnated into the low dielectric glass cloth, it was passed through a slit of a predetermined width to scrape off excess varnish, and dried in a drying oven at 130° C. for a predetermined time to remove toluene, thereby obtaining a prepreg.

[0382] The obtained prepreg was cut into a specified size, a specified number of sheets were stacked, and copper foil (manufactured by Furukawa Electric Co., Ltd., thickness 18 μm, F1N-WS foil) was stacked on both sides of the stacked prepreg, and vacuum pressing was performed in this state to obtain a copper-clad laminate. In the vacuum pressing step, first, 40 kg / cm 2 The temperature was raised from 30°C to 200°C at a rate of 2°C / min. After the temperature reached 200°C, a pressure of 40kg / cm 2 The mixture was maintained at 200° C. for 60 minutes under a pressure of 1.5° C.

[0383] Thereafter, the copper-clad laminate obtained was etched to remove the copper foil, thereby obtaining a laminate as a sample.

[0384] (Examples 8 to 15, Comparative Examples 5 to 17)

[0385] Except for changing the resin composition as shown in Table 3 and Table 4, a resin composition, a varnish, a prepreg and a copper-clad laminate were obtained in the same manner as in Example 7.

[0386] It should be noted that in Comparative Example 15 using PPE6, polyphenylene ether was not completely dissolved in toluene, and thus a prepreg and a copper-clad laminate could not be produced.

[0387] <Evaluation>

[0388] (1) Dielectric properties of cured products of resin compositions

[0389] The cured products of the resin compositions obtained in the above examples and comparative examples were measured for dielectric constant and dielectric loss tangent at 10 GHz by a split cylinder method using a network analyzer (N5227B, manufactured by KEYSIGHT TECHNOLOGIES) and a split cylinder resonator (CR-710, manufactured by EM Labo Co., Ltd.).

[0390] The cured product of the resin composition with a thickness of about 0.5 mm obtained in the above examples and comparative examples was cut into a plate with a length of 50 mm and a width of 50 mm. Then, it was placed in an oven at 105°C ± 3°C and dried for 1 hour, and then left to stand for 24 ± 2 hours at 23°C and a relative humidity of 50 ± 2%. Thereafter, the dielectric constant and dielectric loss tangent were measured by using the above measuring device at 23°C and a relative humidity of 50 ± 2%.

[0391] From the viewpoint of reducing transmission loss, the measured dielectric loss tangent of the cured product of the resin composition is preferably 0.0053 or less, more preferably 0.0050 or less, and even more preferably 0.0049 or less.

[0392] (2) Heat resistance (glass transition temperature) of cured product of resin composition

[0393] The copper-clad laminates obtained in the above examples and comparative examples were subjected to dynamic viscoelasticity measurement, and the temperature at which tan δ was maximum was determined as the glass transition temperature (Tg). A dynamic viscoelasticity device (EPLEXOR 500N manufactured by GABO) was used as the measuring device.

[0394] The cured products of the resin compositions obtained in the above Examples and Comparative Examples and having a thickness of about 0.5 mm were cut into test pieces having a length of 50 mm and a width of about 10 mm and measured in a tensile mode at a frequency of 5 Hz.

[0395] From the viewpoint of dimensional stability during processing, the measured glass transition temperature of the cured product of the resin composition is preferably 203° C. or higher, more preferably 205° C. or higher, further preferably 208° C. or higher, particularly preferably 210° C. or higher.

[0396] (3) Solvent resistance of cured product of resin composition (toluene immersion test)

[0397] The cured products of the resin compositions obtained in the above Examples and Comparative Examples and having a thickness of about 0.5 mm were cut into pieces having a length of 50 mm and a width of 5 mm, and immersed in a sufficient amount of toluene at 20° C. for 24 hours, and the weight reduction was evaluated according to the following criteria.

[0398] ○: When the mass reduction before and after immersion is less than 0.5 mass%

[0399] △: When the mass reduction before and after immersion is 0.5 mass% or more and less than 1 mass%

[0400] ×: When the mass reduction before and after immersion is 1 mass % or more

[0401]

[0402]

[0403] From the results of Tables 3 and 4, it can be seen that when PPE1, 2, 4, and 5 are included, the solubility in toluene is excellent, and by using them, a resin composition having excellent dielectric properties, high heat resistance, and excellent solvent resistance can be obtained. In addition, it can be seen that for each sample of the example, any of the dielectric properties, heat resistance, and solvent resistance are excellent in a well-balanced manner compared to each sample of the comparative example.

[0404] [Example C]

[0405] Cured products of the resin compositions of the respective Examples and Comparative Examples were prepared as follows.

[0406] (Example 16)

[0407] According to the composition and solvent shown in Table 5, a thermoplastic resin was added to 101 parts by mass of toluene, stirred and dissolved, and then a flame retardant, spherical silica, and PPE1 and modified PPE10 synthesized by the above method were added, and stirring was continued until PPE1 and modified PPE10 were dissolved. Then, triallyl isocyanurate and / or triallyl cyanurate, and an organic peroxide were added to the dissolved product, and stirred sufficiently to obtain a varnish.

[0408] After the obtained varnish was impregnated into the L glass cloth, the cloth was passed through a slit of a predetermined width to scrape off excess varnish, and dried in a drying oven at 130° C. for a predetermined time to remove toluene, thereby obtaining a prepreg.

[0409] The obtained prepreg was cut into a specified size, a specified number of sheets were stacked, and copper foil (manufactured by Furukawa Electric Co., Ltd., thickness 18 μm, F1N-WS foil) was stacked on both sides of the stacked prepreg, and vacuum pressing was performed in this state to obtain a copper-clad laminate. In the vacuum pressing step, first, 40 kg / cm 2 The temperature was raised from 30°C to 200°C at a rate of 2°C / min. After the temperature reached 200°C, a pressure of 40kg / cm 2 The mixture was maintained at 200° C. for 60 minutes under a pressure of 1.5° C.

[0410] Thereafter, the copper-clad laminate obtained was etched to remove the copper foil, thereby obtaining a laminate as a sample.

[0411] (Examples 17 to 25, Comparative Examples 18 to 32)

[0412] Except for changing the resin composition as shown in Tables 5 and 6, a resin composition, a varnish, a prepreg and a copper-clad laminate were obtained under the same conditions as in Example 16.

[0413] It should be noted that, in Comparative Examples 22 and 23 in which PPE6 was used, PPE was not completely dissolved in toluene, and thus prepregs and copper-clad laminates could not be produced.

[0414] <Evaluation>

[0415] The samples obtained in the above-mentioned Examples and Comparative Examples were evaluated as follows. The evaluation results are shown in Tables 5 and 6.

[0416] (1) Dielectric properties of cured products of resin compositions

[0417] The dielectric constant and dielectric loss tangent of the cured products of the resin compositions prepared in Examples and Comparative Examples were measured at 10 GHz by a split cylinder method using a network analyzer (N5227B, manufactured by KEYSIGHT TECHNOLOGIES) and a split cylinder resonator (CR-710, manufactured by EM Labo Co., Ltd.).

[0418] The cured product of the resin composition with a thickness of about 0.5 mm prepared by the above method was cut into a plate with a length of 50 mm and a width of 50 mm. Then, it was placed in an oven at 105°C ± 3°C and dried for 1 hour, and then left to stand for 24 ± 2 hours at 23°C and a relative humidity of 50 ± 2%. Thereafter, the dielectric constant and dielectric loss tangent were measured by using the above measuring device at 23°C and a relative humidity of 50 ± 2%.

[0419] From the viewpoint of reducing transmission loss, the measured dielectric loss tangent of the cured product of the resin composition is preferably less than 0.00320, more preferably less than 0.00318, further preferably less than 0.00316, and particularly preferably less than 0.00312.

[0420] (2) Copper foil peel strength of cured product of resin composition (peel strength N / mm)

[0421] The stress when the copper foil of the copper-clad laminate is peeled off at a fixed speed is measured. The copper-clad laminate obtained in the above-mentioned embodiment and comparative example, which uses a 18μm thick copper foil (manufactured by Furukawa Electric Co., Ltd., F1N-WS foil) is cut into a size of 10mm in width × 120mm in length, and an Autograph (manufactured by Shimadzu Corporation, AG-I20kN) is used to measure the average value of the load when the copper foil is peeled off at an angle of 90° relative to the removal surface at a speed of 50mm / minute, and the average value of 3 measurements is obtained.

[0422] In addition, from the perspective of preventing wiring peeling, the calculated copper foil peel strength of the cured product of the resin composition is preferably 0.39 N / mm or more, more preferably 0.52 N / mm or more, further preferably 0.55 N / mm or more, and particularly preferably 0.60 N / mm or more.

[0423] (3) Solvent resistance of cured product of resin composition (toluene immersion test)

[0424] The cured products of the resin compositions obtained in the above Examples and Comparative Examples and having a thickness of about 0.5 mm were cut into pieces having a length of 50 mm and a width of 5 mm, and immersed in a sufficient amount of toluene at 20° C. for 24 hours, and the weight reduction was evaluated according to the following criteria.

[0425] ○: When the mass reduction before and after immersion is less than 0.5 mass%

[0426] △: When the mass reduction before and after immersion is 0.5 mass% or more and less than 1 mass%

[0427] ×: When the mass reduction before and after immersion is 1 mass % or more

[0428]

[0429]

[0430] As shown in Tables 5 and 6, by using PPE 1, 2, 4, 5 in combination with modified PPE 9 to 11, a resin composition and a cured product thereof having excellent dielectric properties, copper foil peel strength and toluene resistance were obtained.

[0431] Industrial Applicability

[0432] The resin composition containing polyphenylene ether of the present invention is excellent in copper foil peel strength and solvent resistance, and therefore has industrial utility value as an electronic material and a modifier.

Claims

1. A polyphenylene ether, characterized in that: It comprises a repeating unit derived from phenol of the following formula (1) and a repeating unit derived from phenol of the following formula (2), With respect to 100 mol % of the total of the repeating units of the following formula (1) and the following formula (2), the content of the repeating units derived from the phenol of the following formula (1) is 70 mol % or more and less than 85 mol %, and the content of the repeating units derived from the phenol of the following formula (2) is greater than 15 mol % and less than 30 mol %, The molecular weight distribution (Mw / Mn) determined by gel permeation chromatography (GPC) is 2.0 to 6.

0. The number of OH groups per molecule is 0.8 to 2.

5. [Chemistry 1] In formula (1), R 11 are each independently a saturated hydrocarbon group having 1 to 6 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom, and R 12 are each independently a hydrogen atom, a hydrocarbon group having 1 to 6 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom, [Chemistry 2] In formula (2), R 22 are each independently a hydrogen atom, a saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms which may be substituted, an aryl group having 6 to 12 carbon atoms which may be substituted, or a halogen atom, and the two R 22 If they are not hydrogen atoms, R 21 is a partial structure represented by the following formula (3), [Chemistry 3] In formula (3), R 31 Each independently represents a linear alkyl group having 1 to 8 carbon atoms which may be substituted, or two R 31 A cyclic alkyl structure having 1 to 8 carbon atoms, R 32 are each independently an alkylene group having 1 to 8 carbon atoms which may have a substituent, b is each independently 0 or 1, R 33 It is a hydrogen atom, an alkyl group having 1 to 8 carbon atoms which may have a substituent, or a phenyl group which may have a substituent.

2. The polyphenylene ether according to claim 1, characterized in that The partial structure represented by the formula (3) is a tert-butyl group.

3. The polyphenylene ether according to claim 1, characterized in that The reduced viscosity (ηsp / c) thereof measured in a 0.5 g / dL concentration chloroform solution at 30°C is 0.13 dL / g to 0.30 dL / g.

4. The polyphenylene ether according to claim 1, characterized in that The number of OH groups per 1 g of the polyphenylene ether is 100 μmol / g to 300 μmol / g.

5. The polyphenylene ether according to claim 1, wherein The monohydric phenol compound represented by the formula (1) is selected from 2,6-dimethylphenol, 2-methyl-6-ethylphenol, 2,6-diethylphenol, 2-ethyl-6-n-propylphenol, 2-methyl-6-chlorophenol, 2-methyl-6-bromophenol, 2-methyl-6-n-propylphenol, 2-ethyl-6-bromophenol, 2-methyl-6-n-butylphenol, 2,6-di-n-propylphenol, 2-ethyl-6-chlorophenol One or more selected from the group consisting of phenol, 2-methyl-6-phenylphenol, 2,6-diphenylphenol, 2-methyl-6-tolylphenol, 2,6-xylenolphenol, 2,3,6-trimethylphenol, 2,3-diethyl-6-n-propylphenol, 2,3,6-tributylphenol, 2,6-di-n-butyl-3-methylphenol, 2,6-dimethyl-3-n-butylphenol and 2,6-dimethyl-3-tert-butylphenol.

6. The polyphenylene ether according to claim 1, characterized in that The monohydric phenol compound represented by the formula (2) is at least one selected from the group consisting of 2-isopropyl-5-methylphenol, 2-cyclohexyl-5-methylphenol, 2-tert-butyl-5-methylphenol and 2-isobutyl-5-methylphenol.

7. The polyphenylene ether according to claim 1, characterized in that It further comprises structural units derived from the following compounds: A phenol compound having two phenol units in the molecule selected from the group consisting of 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 4,4'-methylenebis(2,6-dimethylphenol), bis(4-hydroxy-3-methylphenyl)sulfide, bis(4-hydroxy-3,5-dimethylphenyl)sulfone, α,α'-bis(4-hydroxy-3,5-dimethylphenyl)-1,4-diisopropylbenzene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane and 1,1-bis(2-methyl-4-hydroxy-5-tert-butylphenyl)butane; or 4,4'-[(3-hydroxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[(3-hydroxyphenyl)methylene]bis(2,3,6-trimethylphenol), 4,4'-[(4-hydroxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[(4-hydroxyphenyl)methylene]bis(2,3,6-trimethylphenol), 4,4'-[(2-hydroxy-3-methoxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[(4-hydroxy-3-ethoxyphenyl)methylene]bis(2,3,6-trimethylethylphenol), 4,4'-[(3,4-dihydroxyphenyl)methylene]bis(2,6-dimethylphenol), 4,4'-[( 3,4-dihydroxyphenyl)methylene]bis(2,3,6-trimethylphenol), 2,2'-[(4-hydroxyphenyl)methylene]bis(3,5,6-trimethylphenol), 4,4'-[4-(4-hydroxyphenyl)cyclohexylidene]bis(2,6-dimethylphenol), 4,4'-[(2-hydroxyphenyl)methylene]-bis(2,3,6-trimethylphenol), 4,4'-[1-[4-[1-(4-hydroxy-3,5-dimethylphenyl)-1-methylethyl]phenyl]ethylidene]bis(2,6-dimethylphenol), 4,4'-[1-[4-[1-(4-hydroxy-3-fluorophenyl)-1-methylethyl]phenyl]ethylidene]bis(2,6-dimethylphenol), 2,6-bis[( 4-hydroxy-3,5-dimethylphenyl)ethyl]-4-methylphenol, 2,6-bis[(4-hydroxy-2,3,6-trimethylphenyl)methyl]-4-methylphenol, 2,6-bis[(4-hydroxy-3,5,6-trimethylphenyl)methyl]-4-ethylphenol, 2,4-bis[(4-hydroxy-3-methylphenyl)methyl]-6-methylphenol, 2,6-bis[(4-hydroxy-3-methylphenyl)methyl]-4-methylphenol, 2,4-bis[(4-hydroxy-3-cyclohexylphenyl)methyl]-6-methylphenol, 2,4-bis[(4-hydroxy-3-methylphenyl)methyl]-6-cyclohexylphenol, 2,4-bis[(2-hydroxy-5-methylphenyl)methyl]-6-cyclohexyl Phenol, 2,4-bis[(4-hydroxy-2,3,6-trimethylphenyl)methyl]-6-cyclohexylphenol, 3,6-bis[(4-hydroxy-3,5-dimethylphenyl)methyl]-1,2-benzenediol, 4,6-bis[(4-hydroxy-3,5-dimethylphenyl)methyl]-1,3-benzenediol, 2,4,6-tris[(4-hydroxy-3,5-dimethylphenyl)methyl]-1,3-benzenediol, 2,4,6-tris[(2-hydroxy-3,5-dimethylphenyl)methyl]-1,3-benzenediol, 2,2'-methylenebis[6-[(4 / 2-hydroxy-2,5 / 3,6-dimethylphenyl)methyl]-4-methylphenol], 2,2'-methylenebis[6-[(4-hydroxy-3,5-dimethylphenyl)methyl]-4-methylphenol], 2,2'-methylenebis[6-[(4 / 2-hydroxy-2,3,5 / 3,4,6-trimethylphenyl)methyl]-4-methylphenol], 2,2'-methylenebis[6-[(4-hydroxy-2,3,5-trimethylphenyl)methyl]-4-methylphenol], 4,4'-methylenebis[2-[(2,4-dihydroxyphenyl)methyl]-6-methylphenol], 4,4' -methylenebis[2-[(2,4-dihydroxyphenyl)methyl]-3,6-dimethylphenol], 4,4'-methylenebis[2-[(2,4-dihydroxy-3-methylphenyl)methyl]-3,6-dimethylphenol], 4,4'-methylenebis[2-[(2,3,4-trihydroxyphenyl)methyl]-3,6-dimethylphenol], 6,6'-methylenebis[4-[(4-hydroxy-3,5-dimethylphenyl)methyl]-1 ,2,3-benzenetriol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(2-hydroxy-5-methylphenyl)methyl]phenol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(4-hydroxy-3,5-dimethylphenyl)methyl]phenol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(4-hydroxy-2-methyl-5-cyclohexylphenyl)methyl]phenol], 4,4'-cyclohexylidenebis[2-cyclohexyl-6-[(4-hydroxy-2-methyl-5-cyclohexylphenyl)methyl]phenol], A phenol compound having three or more phenol units in the molecule selected from the group consisting of 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 4,4',4",4"'-(1,2-ethyldimethyl)tetrakis(2,6-dimethylphenol), 4,4',4",4"'-(1,4-phenylenedimethylene)tetrakis(2,6-dimethylphenol) and 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane.

8. A polyphenylene ether solution, characterized in that It contains: The polyphenylene ether according to any one of claims 1 to 7; and One or more solvents selected from the group consisting of toluene, xylene, methyl ethyl ketone, cyclopentanone, cyclohexanone and chloroform.

9. A resin film, characterized in that: The polyphenylene ether comprises the polyphenylene ether according to any one of claims 1 to 7.

10. A prepreg, characterized in that: This is a composite of a substrate and the polyphenylene ether according to any one of claims 1 to 7.

11. The prepreg according to claim 10, characterized in that The substrate is glass cloth.

12. A metal-clad laminate, characterized in that: This is a laminate of a cured product of the resin film according to claim 9 and a metal foil.

13. A metal-clad laminate, characterized in that: This is a laminate of a cured product of the prepreg according to claim 10 and a metal foil.

Citation Information

Patent Citations

  • JP1974000315A

  • Poly(phenylene ether), production method therefor, thermally curable composition, prepreg, and laminate

    WO2022158180A1

  • Method for poly(phenylene ether) manufacture and associated poly(phenylene ether)

    CN107849239A

  • Polyphenylene ether, method for producing same, thermosetting composition, prepreg, and laminate

    CN116867835A

  • Polyphenylene ether, method for producing same, thermosetting composition, prepreg, and laminate

    CN116888186A